Examination of a short-term underwater soundscape in a southeast Chinese Bay - Xuming Peng; Hao Wu; Siguang Liu; Fuxing Wu; Weijie Fu; Fei Zhang; Wenjie Xiang; Wenzhan Ou; Boyu Zhang; Jiayin Wang; Chao Long; Zhongchang Song (Marine Pollution Bulletin, 2026)

Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

Quantitative evaluation of ground disturbance induced by shield tunneling considering soil spatial variability: insights from field monitoring and random finite element analysis - Zhang Hao; Xue Wen-bin; Zhu Lei; Liu Jin-long; Ma Liu-fu; Xiong Feng; Li Peng-fei; Tannant Dwayne (Tunnelling and Underground Space Technology, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Exploring land consolidation solutions towards land use low-carbon transition: Evidence from Shenzhen, China - Haiyue Fu; Xinyi Chen; Penghui Jiang; Ding Fei; Chuan Liao (Land Use Policy, 2026)

Thermodynamically favored fluorine refilling stabilizes oxygen vacancies for ultrafast and wide-temperature aqueous zinc-ion batteries - Daming Chen; Yang Ming; Jimin Fu; Chuanwei Zhi; Zijian Li; Wei Cai; Hanbai Wu; Xin Hu; Rujun Yu; Shou Shi; Jing Liu; De-Yi Wang; et al. (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Seismic response of tunnels with isolation layer crossing fault zones: large-scale shaking table tests and numerical verification - Tong Lu; Hui Zhong; Chen Xue; Fei Ye; Guodong Wang; Wenxi Fu (Tunnelling and Underground Space Technology, 2026)

Integrative multi‑omics and experimental validation reveal that Duhuo Jisheng Decoction alleviates IVDD by inhibiting MAPK signaling‑mediated inflammation, apoptosis, and mitochondrial dysfunction - Fei Liu; Chao Song; Yinjing Luo; Xiaoqiang Wang; Zhangchao Wei; Qian Yan; Zhijiang Fu; Zongchao Liu; Feng Chen (Tissue and Cell, 2026)

Optimized straw–nitrogen management enhances crop yield, soil carbon sequestration, and economic returns in dryland maize systems of Northwest China - Yunfei Ren; Jiayi Li; Fu Liu; Longchuang Zhang; Xiu Chen; Haibo Hu; Xiaoyu Ning; Yeye Zhang; Jinxia Wang; Xiaozhou Li; Shuangguo Zhu; Fei Mo (Soil and Tillage Research, 2026)

Elucidating the physiological and pathological responses of Cyprinus carpio to total dissolved gas supersaturation via combined in situ investigations and laboratory studies - Xiaoqing Liu; Chenjun Fu; Wei Lu; XiaoHan Luo; Fei Wang; Haoran Shi; Yao Yang; Bing Yao; Yuanyi Zhang (Journal of Environmental Chemical Engineering, 2026)

Temperature effects on dissolved organic matter release and plant growth from aged microplastics of different particle sizes - Xin Zhang; Wei Chu; Jiabao Ma; Le Fu; Zhiqi Yang; Xiuping Li; Fei Yu; Jie Ma (Journal of Environmental Chemical Engineering, 2026)

Recent advances in heterologous lactoprotein expression: from host engineering to downstream processing - Yu Qiu; Li Li; Linjie Feng; XiangYu Fan; Xiaolei Fan; Rongbo Guo; Kangqing Fei; Shanfei Fu (Food Bioscience, 2026)

Modulation of juice aroma by water- and alkali-extractable apple polysaccharides: Structure-dependent retention mechanisms - Zhibin Fu; Fei Lao; Wenjiang Dong; Jihong Wu (Food Hydrocolloids, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

ROS-scavenging and immunomodulatory MXene-MnO₂ hydrogel nerve conduit for peripheral nerve regeneration - Tiankun Hui; Yajing Yang; Fei Diao; Haihan Fan; Jie Chen; Yan Li; Yingjie Song; Chenchen Fu; Meijie Jia; Wenwei Han; Tengbo Yu; Jianye Fu (Chemical Engineering Journal, 2026)

Enhanced electrochromic performance of Al-doped NiO films via magnetron sputtering: Experimental characterization and first-principles insights - Weike Zhang; Zeshi Wang; Zhenchao Liu; Lan Zhang; Huizhong Ma; Jinqiu Fu; Fei Wang (Chemical Engineering Journal, 2026)

Low-temperature thermochemical energy storage behavior of Zn-doped phosphogypsum-based calcium sulfate dihydrate: Correlating defect evolution with electronic structure - Fei Mu; Shuai Luo; Meng Fu; Yuanyuan Li; Xuyuan Tang; Yaoqi Huang; Xiaomin Cheng (Chemical Engineering Journal, 2026)

Unraveling the impacts of 2D/3D urban morphology on thermal discomfort: Bridging objective and subjective perspectives under the LCZ framework - Teng Zhang; Baolei Zhang; Yu Cheng; Pingjie Fu; Fei Meng (Building and Environment, 2026)

Multi-environmental biodegradation of a cellulose-based/polylactic acid non-leaching antibacterial composite membrane - Xianpei Xu; Hongbo Wang; Junming Liang; Youbo Di; Mei Liu; Fu Li; Pengfei Fei (Biomass and Bioenergy, 2026)

Visualizing glyphosate: A low-toxicity Zn2+-Based fluorescent probe for rapid detection from field to organism - Yulong Liu; Peng Jiang; Ling Gao; Yang Chen; Anchen Wang; Xianming Zhang; Zishi Wang; Ying Fu; Fei Ye (Analytica Chimica Acta, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Co-treatment of arsenic-rich dust and iron-bearing slag by reduction smelting: Arsenic immobilization, phase transformation, and environmental stability - Fei Chai; Jianhua Wang; Yuan Zhou; Zelin Fu; Yuling Tu; Yanjie Liang; Xiaobo Min; Liyuan Chai (Process Safety and Environmental Protection, 2026)

Greenness may increase ozone-related mortality risk via BVOC emissions: A WRF-CMAQ modeling and population-based study - Jingqiao Fu; Fangrong Fei; Yanchen Zhu; Kai Wu; Xiyao Chen; Feng Chen; Qi Zhao; Mengjie Geng; Yuqing Yao; Xiaoyan Yuan; Jieming Zhong; Xuchao Yang; et al. (Landscape and Urban Planning, 2026)

Coupled carbon and nitrogen cycling respond for organic matter enrichment in a transitional setting during the Early Cretaceous global warming - Fei Wang; Xiugen Fu; Shengqiang Zeng; Puyang Ke; Jianquan Yi; Hengye Wei (Journal of Asian Earth Sciences, 2026)

Echinatin from licorice exhibits antibacterial and anti-biofilm effects against Bacillus cereus: Mechanism and application in milk preservation - Xinrui Li; Senjie Fu; Huan Guo; Jiahao Wang; Xiaoshan Shi; Kai Yin; Jingjing Li; Yanxiang Wang; Junming Tu; Fei He; Xian Xia (International Journal of Food Microbiology, 2026)

Toppling failure mechanism of anti-dip rock slopes under hydrodynamic actions: Insights from centrifuge model tests and numerical simulations - Yang Wang; Fei Ye; Ning Sun; Yinxiang Cui; Qiang Chen; Wenxi Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Bioaugmentation of Rhodococcus ruber F1 achieved simultaneous removals of benzophenone-3 and ammonium - Fei Liu; Chenyu Li; Yuxuan Zhou; Mo Li; Zhicheng Pan; Fu Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2026)

pH and polyphenol-controlled release dual-responsive intelligent hydrogel absorbent pad strategy: methylcellulose‑sodium alginate and anthocyanin@MOFs for chilled pork preservation - Yanpei Huang; Conghui Lang; Fei Ren; Jinsheng Fu; Shengmin Liu; Chuang Zhang; Kai Shan; Chunbao Li; Wenxue Chen; Ming Zhang; Qiujin Zhu; Haiming Chen (Food Research International, 2026)

L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPARα/FABP1/GPX4 pathway to inhibit ferroptosis - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Seismic response and critical acceleration analysis of anti-dip stratified rock slopes: Insights from shaking table tests and numerical simulations - Yang Wang; Qing Lv; Wenxi Fu; Leilei Jin; Fei Ye; Shuai Zhang (Engineering Geology, 2026)

How compound climate shocks reshape urban resilience and scenario-adaptive pathways: New insights from the Yangtze River Economic Belt - Zhiyuan Fu; Fei GAO; Yuchi Li; Shou Zhang; Tianlian Wang (Environmental Impact Assessment Review, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

A green aqueous phase impregnation strategy towards hydrophobic materials for efficient oil-water separation - Rongzhi Li; Gaowei Song; Fei Fu; Minggui Shen; He Liu; Xu Xu (Chemical Engineering Journal, 2026)

The novel PARP-1 inhibitor BMMP-TSC bridges mitochondrial dysfunction and innate immunity via mtDNA leakage and cGAS-STING to suppress breast cancer - Nan Wang; Jianting Huang; Fengshu Fei; Shiyu Ma; Qianlong Fu; Xin Wang; Chuanlong Guo (Chemico-Biological Interactions, 2026)

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Goal-oriented zoning for multifunctional land use: A multi-objective optimization approach to low-carbon transition in Shenzhen, China - Renrong Jiang; Haiyue Fu; Xinyi Chen; Mengmeng Cai; Penghui Jiang; Ding Fei; Chuan Liao (Sustainable Cities and Society, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

GhTUA2 promote roots elongation through regulating cell wall synthesis in cotton - Lizhi Wang; Zailong Tian; Guoyong Fu; Abduvasikov Abduaziz; Daowu Hu; Haobo Zhang; Guangyan Wang; Lu Liu; Hongge Li; Shoupu He; Xiongming Du; Fazliddin Bahromovich Namozov; et al. (Plant Science, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Numerical investigation of dynamic response of HDPE raft-cage aquaculture systems under combined wave-current conditions: Multi-System coupling analysis - Fei Fu; Xiaoying Zhang; Zhanbin Meng; Di Ren; Xiangxi Han; Jianxing Yu; Zhe Hu (Ocean Engineering, 2026)

Anti-collision design and oblique collision analysis of ECC strengthened RC piers with a steel-GFRP-foam fender protection - Yi Cheng; Fei Wang; Wen-Wei Wang; Tianhao Han; Yuan Yue; Jiahui Fu; Yongming Xiong (Ocean Engineering, 2026)

Corrigendum to “L-theanine combined with epigallocatechin gallate to ameliorate alcoholic liver disease in mice by regulating the intestinal flora and activating the PPAR/FABP1/GPX4 pathway to inhibit ferroptosis” [Food Bioscience 83 (September 2026) 109552] - Jiayin Fu; Fei Yan; Dong Qu; Longhua Wang; Xiaohua Chen; Guotao Pu; Wei Yin; Ching Yuan Hu (Food Bioscience, 2026)

Interactive effect between different growth duration variety and cutting height on grain yield and quality in ratoon rice - Jinjuan Zhu; Qimeng Lan; Xinchen Zhang; Hongshun Xiang; Yifan Fu; Huiping Wang; Changzai Zhou; Chen Yang; Guodong Yang; Xing Yu; Chang Zheng; Shen Yuan; et al. (Field Crops Research, 2026)

A mesomechanics-based constitutive model for coarse-grained soils considering particle breakage and grian-size effect - Lu Sun; Sheng Wang; Fu Cao; Enlong Liu; Fei Luo (Computers and Geotechnics, 2026)

Enhancing low-temperature NH3-SCR performance with hollow structure Cu/SAPO-34 catalysts - Xuejie Sui; Zhaoke Meng; Zehui Ma; Weiwei Zheng; Jingrui Yuan; Xuchao Geng; Fei Wang; Yuchao Lyu; Jianye Fu; Lishuang Ma; Xinmei Liu (Chemical Engineering Journal, 2026)

Mo2C nanospheres on biomass-derived N-doped carbon for high-efficiency hydrogen evolution - Huaiyu Jin; Jinfeng Zhang; Enjie Yan; Zuopeng Fu; Fei Xie; Wenjiang Li (Biomass and Bioenergy, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Failure behavior and associated thermal and gas hazards of lithium-ion batteries under typical cargo-fire scenarios in air transport - Fei Li; Zengjiang Zou; Xu Huang; Xudong Cheng; Rong Qiu; Yangyang Fu (Process Safety and Environmental Protection, 2026)

Identification and knockout of SlHDZIV14 reveals fruit trichome-associated control of postharvest water loss in tomato - Ying Fu; Meng Li; Li Huang; Iben Sørensen; Xueting Liu; Chenhuan Fei; Wenran Song; Sen Zhang; Wei Zhang; Kexuan Tang; Jocelyn K.C. Rose; Qian Shen (Postharvest Biology and Technology, 2026)

Zwitterionic engineering of chitosan enables highly soluble, antibacterial films for sustainable fruit preservation - Dahai Liu; Xiaoxiao Wang; Jing Xu; Fang Yang; Riwang Li; Qiang Fu; Jie Li; Jieyan Wang; Xiu Wang; Haotian Lan; Ziyin Liu; Yafei Su; et al. (Food Research International, 2026)

Paeoniflorin's role in inhibiting malignant metastasis of gastrointestinal stromal tumors via CYP3A4 modulation - Dapeng Cui; Zeyin Cui; Yansen Li; Shuang Fan; Lei Li; Cheng Yang; Ruixia Yu; Jiaxin Cui; Runjia Fu; Jiandong Fei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biophotocatalytic and bioelectrocatalytic strategies for methane production and oxidation: emerging pathways and perspectives - Zhenni Cheng; Xiaolei Fan; Rui Li; Kangqing Fei; Rongbo Guo; Shanfei Fu (Archives of Microbiology, 2026)

Genesis of the Zhamuqin Pb−Zn−Ag polymetallic deposit in the middle-southern Great Xing’an Range, NE China: constraints from H−O−S−Pb isotope geochemistry and geochronology - Peng He; Man Li; Shuo Guo; Fei Teng; Xianyu Cheng; Qilong Fu (International Geology Review, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Chemical composition, bioactivity, and applications of Pandanus amaryllifolius leaves: A comprehensive review - Pengyin Li; Tao Fei; Jiamu Kang; Jingtao Cui; Junxia Jiang; Enxi Fu; Weimin Zhang; Tian Li (Trends in Food Science & Technology, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

The Earth’s mantle fuels our future by hosting and emanating natural hydrogen - Tong Liu; Yong-Qiang Hu; Chuan-Zhou Liu; Chang Zhang; Chenhui Fei; Fu-Yuan Wu (Science Bulletin, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Upper-crustal anisotropy in the aftershock zone of the 2021 Ms6.4 Yangbi earthquake from the S-wave splitting analysis - Fei Rao; Tuo Zheng; Haifeng Zhou; Wei Fu; Xiaoping Fan; Hui Zhang; Peng Zhang; Nan Sun (Physics of the Earth and Planetary Interiors, 2026)

Decoupled synergistic control of airborne infection risk and thermal comfort in open layout dental clinics: Integration of indoor airflow pattern, physical barrier, and air purifier - Jingwen Chen; Xinchao Fu; Shuhui Fei; Xing Li; Zhuangbo Feng (Journal of Hazardous Materials, 2026)

Ophiolites in Pakistan: Key evidence for the geodynamic evolution of the Neo-Tethys Ocean - Inayat Ullah; Peng-Fei Zhang; Wen-Jun Hu; Mei-Fu Zhou (Journal of Asian Earth Sciences, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Self-sustaining singlet oxygen Fenton-like catalysis for scalable water remediation - Fu-Qiao Yang; Chang-Wei Bai; Jing Wang; Xin-Jia Chen; Pi-Jun Duan; Zhi-Quan Zhang; Ying Shao; Meng Zhang; Fei Chen (Chemical Engineering Journal, 2026)

Radiative cooling coatings and natural ventilation in urban street canyons: Synergies and trade-offs - Cheng-Peng Ma; Yu-Fei Tang; Shang-Xian Zhao; Gui-Xiong Yang; Fu-Yun Zhao; Yuguo Li; Rongpeng Zhang (Building and Environment, 2026)

Physiological Effects and Yield Potential of Japonica Rice Grown Using Straw-Based Substrate Blocks and Seedbed Conditioner - Yunsheng Song; Yi Jiang; Fei Chen; Minghui Dong; Xiuliang Jin; Yajie Hu; Yu Fu; Zhongying Qiao; Yuxuan Wang (International Journal of Plant Production, 2026)

Daphnetin prevents acute graft-versus-host disease by suppressing donor T cell expansion and function - Zhi-Feng Wei; Yan-Fang Chen; Fei Song; Yu Fu; Yun-Wei Zhang; Tian-Xue Qin; Su-Jun Gao; Long Su (Inflammopharmacology, 2026)

A CRISPR/dCas9 mediated electrochemical impedimetric biosensor for sensitive mtDNA detection - Fei Chen; Mengqin Huang; Shu Zeng; Yi Wan; Anjun Qin; Xinzhe Yang; Danfeng Fu; Masoud Negahdary; Chenghui Zhang (Analytica Chimica Acta, 2026)

Advances, opportunities, and challenges in microbial community construction: from environmental remediation to biomanufacturing - Mengxue Li; Xiang Xing; Kangqing Fei; Zhenni Cheng; Jiayu Zhang; Rongbo Guo; Xiaokui Zhang; Shanfei Fu; Xiaolei Fan (Archives of Microbiology, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Effect of high-pressure homogenization on surfactant-free starch-oil films - Xi-ying Xu; Dong-ming Gao; Xu Yao; Zi-xu Zheng; Zong-qiang Fu; Gang Li; Fei-fei Li (Journal of Food Engineering, 2026)

Dual function of sulfur in Cd-As co-contaminated soils: Enhancing phytoremediation with mustard and ensuring rice safety under drought-flood rotation systems - Fei Miao; Xin Zhang; Qingling Fu; Hongqing Hu; Md․ Shoffikul Islam; Zaibin Yuan; Xiang Wang; Lin Yang; Linchuan Fang; Jun Zhu (Journal of Environmental Sciences, 2026)

Investigation of the dynamic failure behavior and liquefaction resistance of sand under seismic loading - Yajing Li; Hao Wei; Wenxi Fu; Fei Ye; Tong Lu (Journal of Applied Geophysics, 2026)

38 years of micronutrient fertilization, particularly copper, enhance winter wheat yield during drought on the Loess Plateau without yield penalties - Xiaozhou Li; Fu Liu; Yunfei Ren; Jinxia Wang; Haibo Hu; Shuangguo Zhu; Fei Mo (Field Crops Research, 2026)

Development and hypermobility of the Basu rock avalanche in the Nu River ophiolitic mélange, southeastern Tibetan Plateau - Yunjian Gao; Jianhui Deng; Siyuan Zhao; C.F. Lee; Xin Yao; Fuchu Dai; Stuart Lane; Yongbo Tie; Kaiyu Ren; Fei Wang; Ziguo Fu (Engineering Geology, 2026)

A combination of QTL mapping and genome‑wide association study revealed key genes for heat tolerance in maize - Xining Jin; Hangdan Qu; Pingxi Wang; Huaisheng Zhang; Tiantian Li; Xiangyuan Wu; Shilin Chen; Yaqiu Zhao; Fei Wang; Rui Song; Zhiyuan Fu; Xiaoxiang Zhang (Theoretical and Applied Genetics, 2026)

A holistic 3D framework for single-plant point cloud segmentation and phenotypic trait extraction - Tengfei Liu; Weili Sun; Haoyu Jiang; Luxu Tian; Xiuqing Fu; Chenhao Jin; Chenghao Wang; Cairong Chen; Fei Hu (Computers and Electronics in Agriculture, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Secondary metabolites from the endophytic fungus Hypoxylon sp. HK-37 derived from Aquilaria sinensis - Zheng-Zhuo Ren; Kai-Lei He; Fei Wu; Li Yang; Jing-Zhe Yuan; Ze-Sheng Li; Hao-Fu Dai; Wen-Jian Zuo; Hui-Qin Chen (Phytochemistry Letters, 2026)

Design and activity validation of GABA-gated chloride channels allosteric modulators based on computational biology - Siyi Yang; Shuang Gao; Tiansong Li; Jinghu Bi; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Optimal integration of lignin nanoparticles and whey protein distinctively stabilizes high internal phase pickering emulsions for multiple environmental resistances - Guilan Zhao; Qian Zhang; Yongtai Wang; Xiaojie Gao; Fei Huang; Jiale Liu; Hao Peng; Chunxiang Fu; Yanting Wang; Liangcai Peng (Food Chemistry, 2026)

Prebiotic efficacy of green banana flour against antibiotic-associated diarrhea in juvenile mice - Zhengke Fu; Xiaoxia Wang; Yang Liu; Daying Xia; Yilin Song; Fan Xv; Maoshen Chen; Fang Zhong; Fei Liu (Food Bioscience, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Optimization of fermentation conditions for recombinant McXyn0243 xylanase from Malbranchea cinnamomea and its application in producing xylooligosaccharides from sugarcane bagasse - Jinghao Ma; Lin Dai; Ruiwen Cheng; Fei Xiao; Yongbo Qu; Jianshan Fu; Jianhui Wen; Rana Abdul Basit; Dafeng Yin; Guangsen Fan (Biocatalysis and Agricultural Biotechnology, 2026)

Human Amniotic Mesenchymal Stromal Cells Promote Bone Regeneration via Regulating Ameloblastoma-Derived-Bone Marrow Mesenchymal Cells Crosstalk and Autophagy in Ameloblastoma Microenvironment - Yuhuan Xiao; Xiaofeng Fu; Weina Zhou; Jin Li; Bin Yan; Fei Jiang (Tissue Engineering and Regenerative Medicine, 2026)
Background: Growing evidence validates the vital function of mesenchymal stem cells (MSCs) in tumor development. Our previous findings have illustrated the role of MSCs in the invasion and recurrence of ameloblastoma. Stem cells can be transplanted to release paracrine factors in the tumor microenvironment (TME) to inhibit tumor progression and recurrence. The paracrine function of human amniotic mesenchymal stromal cells (HAMSCs) benefits bone regeneration. However, the dual function of HAMSCs in inhibiting tumor progression and promoting bone regeneration in the TME remains unknown. Methods: To analyze the role of HAMSCS in the cross-talk between mesenchymal ameloblastoma-derived cells (M-AMCs), human bone marrow mesenchymal stem cells (HBMSCs), and HAMSCs, an in vitro co-culture system of M-AMCs, HBMSCS, and HAMSCS was prepared. An in vivo ectopic transplantation model was employed further to detect the therapeutic effect of HAMSCs on bone regeneration. Results: A high-level basal autophagy was detected in the stroma of ameloblastoma. In the in vitro co-culture models, M-AMCs suppressed the proliferation, differentiation, migration, and autophagy of HBMSCs, and conversely, HBMSCs promoted the above phenotypes of M-AMCs. HAMSCs promoted the proliferation, differentiation, migration and autophagy of the co-cultured HBMSCs. Additionally, HAMSCs mediated the cross-talk between M-AMCs and HBMSCs. The in vivo ectopic transplantation model indicated that transplanted HAMSCs promoted bone regeneration by inhibiting the growth of M-AMCs and enhancing autophagy, as well as osteogenesis in bone defects of mice. Conclusions: The interaction of M-AMCs and HBMSCs may be associated with ameloblastoma recurrence. HAMSCs regulate the cross-talk between M-AMCs and HBMSCs to increase the autophagic level in the TME, thus inhibiting the progression and recurrence of ameloblastoma and promoting bone regeneration. Therefore, HAMSC-based therapy provides an alternative to facilitate bone regeneration and repair of ameloblastoma-induced bone defects.

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Development of an inactivated H9N2 subtype avian influenza serological DIVA vaccine using the chimeric A/B NA epitope approach - Jingfeng Zhang; Zhiyu Fan; Qunxing Pan; Fei Yu; Huawei Sun; Minhua Sun; Jinping Fu; Jiasheng Song (Veterinary Microbiology, 2026)

Assessing road network resilience to extreme rainstorms: A percolation and hydrodynamic approach - Fei Ma; Rong Fu; Wei Ren; Qing-Chang Lu; Qing Liu; Zhijie Yang; Zhong Ma (Transportation Research Part D: Transport and Environment, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Herbicidal activity mechanism and ecotoxicological study of novel triazolinone PPO inhibitors based on plant-derived allelochemical cinnamic acid - Li-Xia Zhao; Xian-Da Guo; Jia-Xiao Li; Yue-Li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2026)

Breaking the vicious cycle in urethral repair: A Janus hydrogel scaffold with integrated active regulation and passive protection - Yangwang Jin; Fei Qin; Wenzhuo Fang; Meng Liu; Qiang Fu; Ming Yang; Jianguo Ma; Ranxing Yang (Chemical Engineering Journal, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Analytical Model for the Toppling Fracture Depth of Antidip Layered Rock Slopes Under Seismic Loading - Yang Wang; Fei Ye; Leilei Jin; Ning Sun; Shuang Yao; Wenxi Fu (Rock Mechanics and Rock Engineering, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Longifolene and β-ionone promote astaxanthin accumulation in Microcystis aeruginosa by serving signaling function - Lexin Huang; Fei Jiang; Shanshan Song; Xinyuan Zhao; Zhehan Yang; Junjie Ma; Haozhe Xu; Rong Hu; Tianyu Huang; Zhijie Chen; Huiying Fu; Zhaojiang Zuo (Algal Research, 2026)

Ribavirin acts as a candidate insect growth regulator: Providing sustainable control potential for Rhopalosiphum padi - Li Xu; Jingkun Li; Fei Miao; Zhiwen Zhao; Yichen Fu; Hengxu Yan; Sen Huang; Hao Yu; Runqiang Liu; Dongzhi Li (Crop Protection, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Analysis of the effects of different water based extinguishing agents on the electro-thermal performance of 26700 sodium-ion and lithium-ion batteries - Xu Huang; Fei Li; Limei Yan; Feng Xue; Xudong Cheng; Heping Zhang; Yangyang Fu (Process Safety and Environmental Protection, 2026)

Two unprecedented 2-(2-phenylethyl)chromone dimers from the Cambodian agarwood of Aquilaria crassna - Yan Huang; Hao Wang; Wen-Li Mei; Hui-Qin Chen; Fei Wu; Yan-Mei Wei; Wen-Ming Cheng; Hao-Fu Dai (Phytochemistry Letters, 2026)

Resource utilization of multi-source coal-based humic acid residues: Enhancing the remediation potential of cadmium pollution in water-soil-plant systems - Xiaofang Qin; Shuyue Wang; Huaqiang Zhang; Zhanyong Fu; Jingkuan Sun; Jinzhao Ma; Fei Wang; Zhanbin Huang; Zhaohua Lu; Ping Wang; Yaxuan Zhang (Journal of Water Process Engineering, 2026)

Pollutant emission reductions contributed to reducing nitrate level in regional-scale groundwater - Hairu Mao; Guangcai Wang; Fu Liao; Fei Liu; Zheming Shi; Pengpeng Zhou; Chenyu Wang; Hongyu Zhang; Yuqin Wang; Yunfei Bai; Xianglong Chen (Journal of Hydrology, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Proton and water migration regulation drives high-efficiency sulfuric acid concentration via ladder electrodialysis - Ziang Jia; Cong Liu; Ming Tan; Fei Liu; Wei Cong; Rongqiang Fu; Yang Liu; Yang Zhang (Desalination, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Engineering of ethylene glycol (EG)-trophic Escherichia coli enables fast growth on EG for closed-loop PET biodegradation - Jia-Yu Chen; Sheng-Qi Gao; Qing-Song Huang; Xiao-Min Zhao; Qi-Sheng Fu; Kang-Qi Hu; Yan Huang; Jing Wu; Zheng-Fei Yan (Bioresource Technology, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Community assembly governs microbial biogeography and ecosystem multifunctionality across Tibetan alpine grasslands - Xiao-Qian Yang; Jian-Guo Ma; Jian-Fei Yu; Fu-Sen Nan; Yuan-Qi Zhao; Xiao-Bo Wang (Applied Soil Ecology, 2026)

Seedling mycorrhization increases maize yield without altering soil properties: A field study - Rongbin Yin; Zhipeng Hao; Youran Ma; Wei Fu; Hui Wu; Fei Xue; Mengyao Sun; Weiqi Wang; Xin Zhang; Baodong Chen (Applied Soil Ecology, 2026)

Multi-View 3D Reconstruction of Ship Hull via Multi-Scale Weighted Neural Radiation Field - Han Chen; Xuanhe Chu; Ming Li; Yancheng Liu; Jingchun Zhou; Xianping Fu; Siyuan Liu; Fei Yu (Journal of Marine Science and Engineering, 2026)
The 3D reconstruction of vessel hulls is crucial for enhancing safety, efficiency, and knowledge in the maritime industry. Neural Radiance Fields (NeRFs) are an alternative to 3D reconstruction and rendering from multi-view images; particularly, tensor-based methods have proven effective in improving efficiency. However, existing tensor-based methods typically suffer from a lack of spatial coherence, resulting in gaps in the reconstruction of fine-grained geometric structures. This paper proposes a spatial multi-scale weighted NeRF (MDW-NeRF) for accurate and efficient surface reconstruction of vessel hulls. The proposed method develops a novel multi-scale feature decomposition mechanism that models 3D space by leveraging multi-resolution features, facilitating the integration of high-resolution details with low-resolution regional information. We designed separate color and density weighting, using a coarse-to-fine strategy, for density and a weighted matrix for color to decouple feature vectors from appearance attributes. To boost the efficiency of 3D reconstruction and rendering, we implement a hybrid sampling point strategy for volume rendering, selecting sample points based on volumetric density. Extensive experiments on the SVH dataset confirm MDW-NeRF’s superiority: quantitatively, it outperforms TensoRF by 1.5 dB in PSNR and 6.1% in CD, and shrinks the model size by 9%, with comparable training times; qualitatively, it resolves tensor-based methods’ inherent spatial incoherence and fine-grained gaps, enabling accurate restoration of hull cavities and realistic surface texture rendering. These results validate our method’s effectiveness in achieving excellent rendering quality, high reconstruction accuracy, and timeliness.

Three-Dimensional Model Reconstruction of Intact Shale Gas Reservoir Based on the Composition, Structure, and Content of Different Components - Weidong Xie; Yu Liu; Xiaofei Fu; Haixue Wang; Huajun Gan; Hua Wang; Veerle Vandeginste; Jiyao Wang; Fei Jiang (Journal of Earth Science, 2026)

Low-dose chlorine disinfection poses a greater potential risk of antibiotic resistance genes and their pathogenic hosts - Qiyue Meng; Jia Wang; Kun Li; Yibo Zhang; Ziyu Hu; Feng Wang; Fei Pan; Jie Fu; Chenyuan Dang (Water Research, 2026)

Increased microbial extracellular polymeric substances as a key factor in deep soil organic carbon accumulation - Mengxi Feng; Ming Zhang; Peng Cai; Yichao Wu; Qingling Fu; Xin Zhang; Fei Miao; Wen Xing; Shuiqing Chen; Ke-Qing Xiao; Yong-Guan Zhu (Soil Biology and Biochemistry, 2026)

Discovery, herbicidal activity evaluation, and mechanism of action of Heteroaryl chalcones as novel HPPD inhibitors - Li-xia Zhao; Dmitry B. Rubinov; Pan-xiu Zhang; Veronica G. Zinovich; Wen-qing Yu; Tatyana S. Khlebnicova; Fei Ye; Ying Fu; Fedor A. Lakhvich (Pesticide Biochemistry and Physiology, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The Hongjianbingshan W–Li–(Be) deposit in the Beishan Orogenic Belt is not related to carboniferous magmatic–hydrothermal events: Insights from multi-mineral U-Pb and zinnwaldite Rb-Sr geochronology - Yong Yin; Heng-Feng Zhang; Zhuang Duan; Bing-Fei Yu; Heng Luo; Yan-Gang Fu; David R. Lentz; Tao Luo; Ke-Yu Ren; Zhe Ren; Hao Hu (Journal of Geochemical Exploration, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

SlMYB2: an R2R3-MYB transcription factor enhancing drought, salt, and cadmium tolerance in Solanum lycopersicum - Shan Fu; Fei Liu; Ying Li; Chunyan Lu; Tiantian Liu; Songzhou Tian; Wei Jin; Pingan Guo; Liang Chen; Xinxin Geng (Plant Cell Reports, 2026)

HSPA8 lactylation attenuates neuronal pyroptosis via E3 ligase-mediated NLRP3 degradation after ischemic stroke - Jing Fu; Liang Yu; Nengwei Yu; Ping Ni; Chaohui He; Qiao Chen; Suping Li; Fei Xu (Apoptosis, 2026)

Dynamic Mutual Adversarial Learning for Semi-Supervised Semantic Segmentation of Underwater Images with Limited and Noisy Annotations - Han Chen; Ming Li; Yancheng Liu; Jingchun Zhou; Xianping Fu; Siyuan Liu; Fei Richard Yu (Journal of Marine Science and Engineering, 2025)
Swift and accurate semantic segmentation of underwater images is key for precise object recognition in complex underwater environments. Nonetheless, the inherent complexity of these environments and the limited availability of labeled data pose significant challenges to underwater image segmentation. Traditional deep learning methods struggle to cope with limited and noisy annotations. In this paper, we delineate the formulation of a novel semi-supervised paradigm with dynamic mutual adversarial training for the semantic segmentation of underwater images. This paradigm identifies the sources of inaccuracies in pseudo-labeling by analyzing different confidence maps, generated by models with unique prior knowledge. A dynamic reweighing loss function is then employed to orchestrate the mutual instruction of two divergent models. Furthermore, the delineation of confidence map is facilitated via adversarial networks, which involves simultaneous adversarial refinement of the discrimination network and the segmentation model, using the predictions with high-confidence maps as pseudo-labels. Experimental results on public underwater datasets verify that the proposed method can effectively improve semantic segmentation performance under the condition of a small amount of labeled data.

Effects of River Input on the Inorganic Nitrogen Components in Estuary–Bay Waters: Zhanjiang Bay, China - Fei Yue; Zi-Liang Chen; Ying-Ying Zeng; Guo-Huan Yang; Ji-Biao Zhang; Peng Zhang; Miao-Jian Fu (Journal of Marine Science and Engineering, 2025)
Rivers discharge a substantial amount of nutrients into the bay, which constitutes a key area of research in water pollution and environmental management. However, research on the influence of river input on various nitrogen components in semi-enclosed bays like the Zhanjiang Bay remains limited. This study conducted on-site monitoring and cultivation experiments in Zhanjiang Bay. Consequently, a systematic investigation was conducted on the influence of river inputs on the migration and change in different nitrogen components, primarily dissolved inorganic nitrogen (DIN). The results showed that the DIN flux during the rainy season was the greatest input flux, amounting to 9724 t, which accounted for 45.6% of the annual DIN flux. The fluxes of NO2-N and NO3-N were the highest during the rainy season, accounting for 49% and 52% of the total annual flux, respectively. Based on on-site cultivation under different salinity conditions (5, 15, and 25), the DIN content decreased much faster in lower-salinity waters, with the highest average daily change rate of −16.3 μmol/dm3 in a salinity of 5. This indicated that hydrodynamic mixing and exchange processes have a significant impact on the variations in inorganic nitrogen components. Therefore, the results of this study provide valuable insights into the migration and change in inorganic nitrogen components in estuarine water bodies. It also holds significance for guiding the treatment of environmental pollution in estuaries, such as addressing the sewage discharge from the steel industry.

Significant enhancement of photoproduced reactive intermediates in liquid-like region in frozen surface water for micropollutant degradation - Yu Zeng; Mingyang Zhang; Shuyao Zhou; Qinglong Fu; Fei Peng; Jinsong Liu; Yujun Wang; Dongmei Zhou; Guodong Fang (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Investigation of the minimum safe thickness of water-resistant strata in vertically layered karst tunnels considering seismic action - Guangchao Lyu; Fei Ye; Qianfeng Xiao; Wenxi Fu (Tunnelling and Underground Space Technology, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Mid-Holocene sea-level change in the northern South China Sea inferred from coral microatolls: constraints on glacial isostatic adjustment and neotectonic activity - Fei Tan; Guotao Zhang; Guowei Fu; Mingzhuang Wang; Yunfeng Zhang; Qi Shi; Xiyang Zhang; Li Cao; Jian‐xin Zhao; Hongqiang Yang (Quaternary Science Reviews, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Numerical investigation of dynamic response in HDPE floating raft array for aquaculture: Coupled system analysis and sea trial evidence - Fei Fu; Zhe Hu; Xiaoying Zhang; Zhanbin Meng; Jianxing Yu (Ocean Engineering, 2025)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

Ore-forming mechanism of high-grade iron ore in Qidashan iron deposit, Liaoning Province: insights from the columbite-group minerals in granite and altered rocks - Yu-zeng Yao; Chang-ming Wei; Jing Liu; Jian-fei Fu; Sheng Xu (Journal of Asian Earth Sciences, 2025)

Performance and toxicity assessment of photocatalytic degradation of sulfanilamide by g-C3N4 nanosheets constructed using temperature gradient regulated etching - Yujie Jiao; Yaqi Mao; Fei Fu; Yongxia Ma; Ru Li; Qikai Liu; Jiali Lei; Sujin Lu; Yang Liu (Environmental Research, 2025)

Origin and genesis of post-collisional intrusive rocks in South Tibet and Himalaya: A review - Zhang-Jian Wu; Peng Gao; Yan Wang; Hui-Chan Huang; Zi-Fu Zhao; Yong-Fei Zheng (Earth-Science Reviews, 2025)

Confinement-accelerated local *CO spillover at semi-enclosed tandem heterointerface for efficient CO2-to-C2 conversion - Zhi-Yuan Wang; Guoqiang Lu; Mulin Yu; Yu-Feng Tang; Peng-Fei Sui; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Regulation of pine wood pretreatment and pyrolysis by hydrogen bond donors in choline chloride deep eutectic solvents - Shuheng Zhao; Shang Wang; Zhuojie Li; Qiaolong Zhai; Junhao Hu; Kui Wang; Fei Fu; Jianjun Hu (Chemical Engineering Journal, 2025)

Screening of Lactic Acid Bacteria Strains from Chinese Fermented Food (Suanshui) and its Protective Effect on Acute Liver Injury in Mice - Fei Wang; Xiang Li; Qi Wang; Qian Jin; Shujie Xu; Li Tang; Zihan Zeng; Aikun Fu; Jinhui Zhu; Qiao Zhang; Rongchang Yang; Yingping Xiao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Assessing the potential of seedling-carried iron plaques on root to reduce As accumulation in rice: insights from the biotic/abiotic role of 'new' iron plaques formation - Xin Zhang; Hongqing Hu; Fei Miao; Mengxi Feng; Linchuan Fang; Jun Zhu; Qingling Fu (Plant and Soil, 2025)

Identification of a missing Pictet–Spenglerase in the Gloriosa superba L. colchicine biosynthesis pathway - Jingyi Sun; Huapeng Sun; Zhiqiang Xiong; Xuefei Jiang; Xiaona Fu; Hanqing Cong; Fei Qiao (Molecular Biology Reports, 2025)

DDX1 facilitates lenvatinib resistance in hepatocellular carcinoma through regulating ephrin-A3 and activating the Wnt/β-catenin signaling pathway - Shenglan Huang; Hua Wang; Shumin Fu; Fei Cheng; Kan Liu; Jianbing Wu (Functional & Integrative Genomics, 2025)

Quantitative estimation of the spatiotemporal responses of PM2.5 and O3 synergistic pollution to precursors in the Chengdu-Chongqing City Group of China - Mingliang Ma; Yihong Jiao; Mengjiao Liu; Mengnan Liu; Fei Meng; Huaqiao Xing; Jingxue Bi; Yuqiang Wang; Tongwen Liu; Pingjie Fu (Air Quality, Atmosphere & Health, 2025)

Full waveform inversion of cross-hole GPR data using Markov Chain Monte Carlo method based on SE-Resnet - Sheng-chao Wang; Yu-fei Wang; Yi-fei Liu; De-fu Zhang; Hui Sun; Gong-min Chen; Xiang-yu Tan (Applied Geophysics, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Recent advances in the discovery of novel bleaching herbicides inspired by natural products - Tengfei Ma; Tiansong Li; Yi Zhang; Fedor A. Lakhvich; Tatyana S. Khlebnicova; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2025)

Inspired by mussels for confined adhesion strategy for smart controlled release with pH-responsive in targeted pesticide application and Botrytis cinerea prevention - Yan Zhang; Hailan Wei; Anqi Wang; Fengrui Li; Lixia Zhao; Shuang Gao; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Evolution of immunoglobulin M (IgM) structure and function in vertebrates: A comprehensive review - Shun Yang; Lu-Chuan Zhao; Fu-Zhen Guo; Hong-Sen Xu; Meng-Meng Huang; Hui Fei (Fish & Shellfish Immunology, 2025)

Coupled effects of rainfall-induced soil moisture and nitrogen placement depth on maize productivity and resource utilization in the Loess Plateau - Fu Liu; Peng Wu; Yajuan Li; Shengtong Ma; Nannan Li; Fei Mo; Zhikuan Jia (Field Crops Research, 2025)

Differentiating biosynthesis from heterotrophic nitrification/aerobic denitrification for total-nitrogen removal - Fei Liu; Danyang Zhu; Yaxin Chen; Jin Luo; Yuxuan Zhou; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Environmental Research, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Investigation on the stability of loose soil slope considering the coupling effect of seepage and runoff: theoretical analysis and flume test - Yang Wang; Yufeng Wei; Fei Ye; Qianfeng Xiao; Guangcao Lv; Wenxi Fu (Bulletin of Engineering Geology and the Environment, 2025)

MCNet: a multi-source remote sensing image cascade network for accurate and efficient tailings pond segmentation - Pan Wang; Hengqian Zhao; Zhiguo Liu; Fei Xu; Hancong Fu; Jihua Mao (Advances in Space Research, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Evaluating multifunctional performance of green roofs in rainstorm events: The role of modifiers in substrate layer - Chen Xu; Yiming Fei; Aozhan Liu; Shujiang Miao; Dafang Fu (Journal of Hydrology, 2025)

Reducing nitrogen application through deep placement to optimize the nitrogen balance in a dryland maize cropping system - Fu Liu; Haibo Hu; Xue Li; Zhikuan Jia; Fei Mo (Journal of Cleaner Production, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Integrating hydrogeochemical characterization and multivariate statistics for the source identification and health risk assessment of groundwater pollution in the Ze Zhou Basin, Northern China - Jiamei Fu; Jiawei Chen; Fei Liu; Xiaoyan Zheng; Chenhui Guo; Yunrong Dai (Environmental Pollution, 2025)

3D crosslinked semi-interpenetrating single-ion hybrid electrolytes for dendrite-free and high-voltage lithium metal batteries - Xiao Wang; Puyan Huang; Yuwei Zhong; Shicheng Zhang; Jifang Fu; Yu Ding; Liya Chen; Guorong Chen; Fei Lv; Shuai Yuan (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Delivery of Hexaconazole by the Carboxymethylcellulose grafting and Cellulase/pH responsiveness hollow mesoporous silica nanoparticles - Shuang Gao; Xinyu Guo; Fengrui Li; Yu Zhang; Yanan Yu; Ying Fu; Fei Ye (Carbohydrate Polymers, 2025)

Synthesis and biological evaluation of triazole alcohols containing an indole-3-methyl(phenyl)amino side chain against fluconazole-resistant Candida albicans - Zefei Fan; Lijiao Yang; Jidong Wang; Yafei Hou; Fei Zou; Tianyu Zhang; Yongyan Fu; Yue Zhang; Ruirui Wang; Shichong Yu; Guanghui Ni (Medicinal Chemistry Research, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Improving the prediction of vegetation carbon, phosphorus, and C:P ratio of alpine grassland in the Three-River Headwater Region by combining the field and laboratory reflectance spectroscopy - Shuangyin Zhang; Baocheng Zhao; Xu Jian; Junlin Fu; Yiyun Chen; Teng Fei (Soil and Tillage Research, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

The biocontrol effect and mechanism of the marine-derived fungus Epicoccum nigrum against Alternaria alternata, the causal agent of tomato black spot disease - Si-Qi Fu; Fei Cao; Sen Pang; Xiao-Qian Qi; Zhi-Hong Xu; Ya-Hui Zhang; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu (Pesticide Biochemistry and Physiology, 2025)

Evaluating the potential impacts of mesoscale eddies on the distribution and abundance of an environmentally sensitive squid species (Sthenoteuthis oualaniensis) in the Arabian Sea - Yingyue Fu; Xiaoci Wu; Pengchao Jin; Xinjun Chen; Qinwang Xing; Fei Chai; Jie Cao; Wei Yu (Marine Environmental Research, 2025)

In-situ stabilization of conjugated microporous polymer on sieve plates for multifunctional applications: Detection and removal of aflatoxins - Fei Ma; Yajie He; Fen Tang; Lina Fu; Liangxiao Zhang; Peiwu Li; Li Yu (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Adsorption and coarsening of gold nanoparticles in iron (oxyhydr)oxides lead to high-grade gold mineralization - Feng-Xia Huang; Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Xin-Fu Zhao; Yong Wei; Wei Feng; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2025)

Numerical investigation on prestressed shear key splice connections for onshore wind turbine foundations - Dongliang Zhang; Wantong Liu; Fei Wang; Zhe Yu; Xiangguo Wu; Tianhao Li; Kun Fu; Anish Thapa Magar; Hyeon-Jong Hwang; Xiangping Xian (Engineering Structures, 2025)

Efficient mineralization of antibiotics by novel manganese oxide-based Fenton-like systems: Enhanced performance, toxicity reduction, and life-cycle sustainability - Fu-Qiao Yang; Xin-Tong Huang; Chang-Wei Bai; Zhi-Quan Zhang; Pi-Jun Duan; Fei Chen (Chemical Engineering Journal, 2025)

ZSM-5/Y composite zeolite enabled via ZSM-5 refabrication and outstanding performance of the composite in VGO catalytic cracking - Fei Wang; Chao Feng; Yaxuan Xie; Qiang Ma; Zehui Ma; Huiyi Liu; Yuchao Lyu; Jianye Fu; Lishuang Ma; Xinmei Liu (Chemical Engineering Journal, 2025)

Remobilization of Ni in framboidal pyrite within sulfide nodules in Early Cambrian nickeliferous black shales - Xu-Yang Liu; Ya-Fei Wu; Daniel D. Gregory; Katy Evans; Anthony E. Williams-Jones; Wen Zhang; Mei-Fu Zhou; Jian-Wei Li (Chemical Geology, 2025)

Corrigendum to “Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae” [Aquatic Toxicology, 284 (2025) 107402] - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Dynamical Properties and Empirical Model of Three Typical Rocks in Western China via Cyclic Loading and Unloading Tests - Yang Wang; Qianfeng Xiao; Bin Duan; Leilei Jin; Fei Ye; Wenxi Fu (Rock Mechanics and Rock Engineering, 2025)

A new network-level multi-objective optimization of the heat rejection system for megawatt space nuclear power systems - Yiheng Fei; Jianghan Fu; Chenglong Wang; Suizheng Qiu (Annals of Nuclear Energy, 2025)

Potato–rice and garlic–rice rotation increases soil phosphorus availability through phosphate-solubiliing bacteria and root exudates in upland–paddy cropping systems - Qi Liu; Wei Zhou; Zhiping Yang; Tao Wang; Yong Fu; Xueping Yue; Haixiao Xia; Youfeng Tao; Fei Deng; Xiaolong Lei; Yong Chen; Wanjun Ren (Agriculture, Ecosystems & Environment, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

One-step fabrication of PVDF/BTMSPA composite membranes for enhanced n-butanol/water separation - Sainan Hu; Zhixiang Fu; Yongchao Chen; Chuyu Zhou; Zhengdong Fei (Journal of Environmental Chemical Engineering, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

Research on the Influence of Hydrofoil Propulsive Parameters on Propulsion Efficiency - Meng Cui; Zhihao Liu; Fei Lu; Jiaye Gong; Zheng Fu (Journal of Marine Science and Engineering, 2025)
Oscillating hydrofoils can be used to simplify the study of the swinging caudal fin propulsive mode of fish, where the motion parameters have a direct impact on the hydrodynamic performance and propulsive efficiency. In this study, numerical calculations were carried out on two-dimensional hydrofoils for sinusoidal and non-sinusoidal heave oscillation, and the numerical results of sinusoidal hydrofoils were compared with the experimental values, which were in good agreement. An analysis of how different motion parameters of the sinusoidal hydrofoil affect the hydrodynamic performance was conducted, and the recommended operating condition range was given in combination with the flow field analysis. A unique non-sinusoidal curve was defined, which can enable the motion to enter the crest and trough earlier or later. The parameters for controlling the degree of non-sinusoidal were also defined. A detailed discussion was carried out on how the non-sinusoidal parameters affect the hydrodynamic performance and the change in the flow field. The corresponding recommended working conditions and application scope were given. Further studies can reveal the propulsive mechanism of the swinging caudal fin and provide a reference for the engineering and design of the next generation of bionic fish.

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Theoretical and numerical study of the failure mechanism and minimum safety thickness of water-resistant rock mass in layered karst tunnels - Qianfeng Xiao; Yang Wang; Yajing Li; Leilei Jin; Wenxi Fu; Fei Ye (Tunnelling and Underground Space Technology, 2025)

SEBS-amended in-situ mixed wall material for diesel-contaminated groundwater management - Zhe-Yuan Jiang; Xian-Lei Fu; Fei Jin; Chi Che; Zhong-Yuan Li; Guojun Cai; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Fabrication and characterization of betulin/hydroxypropyl-beta-cyclodextrin inclusion complex nanofibers: A potential edible antibacterial and antioxidant packaging material - Shuang Gao; Yu Zhang; Ruichi Wang; Fengrui Li; Yan Zhang; Siyu Zhu; Hailan Wei; Lixia Zhao; Ying Fu; Fei Ye (Food Chemistry, 2025)

Effective physical methods for aflatoxin B1 removal in food: A comprehensive review - Qingwei Cai; Lixiang Zhu; Peng Chen; Huitao Liu; Teck-Peng Loh; Zhenhua Jia; Jinling Li; Fei Fu (Food Control, 2025)

Fe-doped H2TiO3 for rapid and efficient lithium extraction from shale gas wastewater - Yuchun Ren; Dandan Zhao; Chen Fu; Fei Zhou; Qian Wang; Yongsheng Fu; Tao Gong; Zhenglian Wu (Desalination, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Toxic effects of anionic polyacrylamide on the developmental stages of Oryzias melastigma embryos and larvae - Xinya Zhao; Jiangwei Zan; Zhaohui Sun; Xiangping Xue; Hai Ren; Huiru Fu; Fei Si; Xiaomin Jin (Aquatic Toxicology, 2025)

Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

The application of multi-arc volumetric modulated arc therapy and fixed-field intensity modulated radiotherapy in the treatment of gynecologic cancer with large planning target volume - Jia-Ling Song; Yi-Zhao Zhang; Zhi-Long Zhang; Zheng-Feng Fu; Peng-Fei Sun (Physical and Engineering Sciences in Medicine, 2025)

Plasma proteins and herpes simplex virus infection: a proteome-wide Mendelian randomization study - Canya Fu; Wenjie Xu; Xia Xu; Fei Zhao; Canjie Zheng; Zhiying Yin (Virus Genes, 2025)

Plant and microbial communities follow fast-to-slow strategies in response to grazing in an arid rangeland - Jian-Guo Ma; Jian-Fei Yu; Xiao-Bo Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2025)

A novel varicosavirus associated with Orychophragmus violaceus in China - Yuanling Chen; Qian Li; Jiaping Yu; Yali Zhou; Shifang Fei; Jianxiang Wu; Shuai Fu (Archives of Virology, 2025)

The responses of stress tolerance, physiological performance and energy metabolism to acclimation temperature between tropical and temperate fish species - Yong-Fei Zhang; Ping Xiang; Shi-Jian Fu (Frontiers in Marine Science, 2025)
The responses of stress tolerance and other critical physiological functions of fish species to temperature fluctuations, and the potential relationships with their thermal history and natural habitat conditions, are vital for future population dynamic and distribution. In the present study, the thermal and hypoxia tolerance capacities, oxygen uptake capacity, swimming capacity and energy metabolism traits of two tropical and two temperate fish species acclimated at three temperatures were measured. Two tropical species exhibited much poorer cold tolerance than temperate species as expected. However, irrespective of thermal history, the two species preferred small and stagnant waterbody habitats exhibited greater heat tolerance capacity, lower swimming capacity, higher oxygen supply capacity. hence, higher hypoxia tolerance than the two species preferred to open waterbody. As anticipated, thermal tolerance capacity changed in parallel with acclimation temperature. However, hypoxia tolerance appeared to be the least sensitive to the acclimation temperature, suggesting it is the vital and conservative physiological function for aquatic breathe animals. One of the underlying mechanisms is the parallel increase in oxygen supply capacity with the increased energy and oxygen demanding by higher acclimation temperatures. All variables involved swimming capacity and metabolic parameters were more sensitive in the two tropical species, whereas one eury-thermal species was the least sensitive to temperature change. Moreover, the present study also suggests that in some species, maximum metabolic rate elicited by locomotion and digestion might exhibit different temperature sensitivity ranges, possibly as a result of long-term evolution in response to either habitat environment or life history traits. Nevertheless, the present study suggests that the difference in stress tolerance and other physiological functions, and their sensitivity to temperature, are shaped by both thermal history and habitat conditions. It provides important information for field conservation and the fisheries industry.

Simultaneous adsorption of cadmium and arsenic by goethite-modified rice straw-derived biochar in water and soil: interactive ion effects and co-adsorption mechanism - Iftikhar Ali Ahmad; Hongqing Hu; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Fei Miao; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Ayaz Ali (Environmental Monitoring and Assessment, 2025)

Near-complete assembly and comprehensive annotation of the wheat Chinese Spring genome - Zijian Wang; Lingfeng Miao; Kaiwen Tan; Weilong Guo; Beibei Xin; Rudi Appels; Jizeng Jia; Jinsheng Lai; Fei Lu; Zhongfu Ni; Xiangdong Fu; Qixin Sun; et al. (Molecular Plant, 2025)

MXene-bridged HMO/PSF adsorptive membrane for selective lithium recovery from shale gas wastewater with suppressed Mn leaching - Yuchun Ren; Dandan Zhao; Fei Zhou; Yuan Liu; Chen Fu; Yongsheng Fu; Tao Gong; Zhenglian Wu; Xinyu Yang; Zefeng Cai (Desalination, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Physiological and molecular evidence for phycobilisome degradation in maintaining carbon and nitrogen balance of cyanobacteria - Zhen Luo; Shuangqing Li; Muhammad Zain Ul Arifeen; Fei‑xue Fu; Huayang Gao; Taoran Sun; Lingmei Liu; Xumei Sun; Xinwei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2025)
Phycobilisomes (PBS), the primary light-harvesting complexes in cyanobacteria, are degraded under nitrogen starvation to provide nitrogen for cell growth. This study reveals that carbon supply is a critical prerequisite for PBS degradation under nitrogen deficiency in Synechococcus sp. PCC 7002. Even under nitrogen-deficient conditions, PBS degradation is inhibited in the absence of sufficient carbon. We demonstrate that both the nblAB -mediated PBS-degradation pathway and the ccmLMNK operon-mediated CO 2 -concentrating mechanism are essential for PBS degradation. Furthermore, our findings highlight the critical role of PBS degradation in cyanobacterial adaptation to high C/N conditions. Mutant strains (Mut- nblA and Mut- nblB) deficient in PBS degradation exhibited impaired adaptation to high C/N conditions, as evidenced by their inability to thrive in high NaHCO 3 (nitrogen-free) or CO 2 (low-nitrogen) environments. While these mutants displayed a greener phenotype under high C/N conditions compared to the wild type, they exhibited extensive cellular damage, and significant downregulation of photosynthesis-related genes. These results provide novel insights into the carbon-dependent regulation of PBS degradation and its essential role in cyanobacterial C/N balance, highlighting its significance for their adaptation to fluctuating environmental conditions.

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Energy production and denitrogenation performance by sludge biochar based constructed wetlands-microbial fuel cells system: Overcoming carbon constraints in water - Boda Ouyang; Zhiyong Zhang; Fuzhi Chen; Fei Li; Ming-Lai Fu; Huachun Lan; Baoling Yuan (Water Research, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Eco-friendly approach utilizing banana peel as a renewable additive for Portland cement - Jin Yang; Zhiliang Dong; Ying Su; Cong Tian; Fei Dai; Zhuoyi Fu; Gaoyuan Zhai; Bohumír Strnadel; Xingyang He (Sustainable Chemistry and Pharmacy, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Machine learning prediction for the removal of As and Cd from co-contaminated water by iron-modified biochar from As-enriched P. vittata - Mengxi Feng; Xin Zhang; Hongqing Hu; Fei Miao; Jun Zhu; Linchuan Fang; Qingling Fu (Journal of Water Process Engineering, 2025)

Impacts of sulfamethoxazole on heterotrophic nitrification-aerobic denitrification bacteria and its response strategies: Insights from physiology to proteomics - Teng-Fei Ma; Xiao-Yao Yu; Chong-Yang Xing; Hui-Min Fu; Hao-Yang Duan; You-Peng Chen (Journal of Environmental Management, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Dry season residual straw reduces nitrous oxide emissions during rice season in upland-paddy rotation systems by inhibiting soil denitrification - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Zhiping Yang; Yong Fu; Xueping Yue; Fei Deng; Xiaolong Lei; et al. (Biology and Fertility of Soils, 2025)

The migration pattern of oxidation fluids and its constraints on uranium mineralization in the Tamusu sandstone type uranium deposit of the Bayingobi Basin, China - Chengyong Zhang; Fei Xia; Wei Deng; Xu Liu; Qunxi Zhang; Beibei Shi; Haixiao Li; Yukun Fu (Sedimentary Geology, 2025)

Re-exploration of phenolic compounds from natural waste rice husks: Combined synthesis of novel herbicide and evaluation of herbicidal activity - Li-xia Zhao; Ruo-nan Song; Jing-yi Li; Yue-chun Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2025)

Deoxygenation preceding the Carnian Pluvial Episode (Late Triassic) in the Qiangtang Basin (Tibetan Plateau): Implications for organic and inorganic geochemistry and petrography - Fei Lin; Jian Wang; Ahmed Mansour; Xiugen Fu; Shaohua Su; Ying Nie; Mohamed S. Ahmed; Shengqiang Zeng; Xueren Li (Marine and Petroleum Geology, 2025)

How Rhodococcus ruber accelerated denitrification with soybean-processing wastewater as the electron donor - Haiyun Zhang; Yue Ma; Fei Liu; Songyun Chen; Xu Peng; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Management, 2025)

Enhancing anammox granular sludge for mainstream anammox process by adding iron-loaded diatomite: Performance and intrinsic mechanism - Fanghua Xing; Xuejie Ma; Binbin Sun; Tao Wang; Fei Lian; Luyao Wang; Ziyi Fu (Environmental Research, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Formation mechanism and prediction of rockbursts in tuff tunnels in shallow buried sections of gullies: A case study - Junfu Fu; Junru Zhang; Bin Li; Zhijian Yan; Fei Song; Xinan Yang (Tunnelling and Underground Space Technology, 2025)

Fucoxanthin ameliorates ulcerative colitis by maintaining the epithelial barrier via blocking JAK2/STAT3 signaling pathway - Jingjing Ma; Simei Yue; Yinghui Liu; Lingjiao Gong; Pengzhan He; Yingjie Yang; Zhengxin Fu; Danxiang Han; Qiang Hu; Fei Liao; Lin Xu (Toxicology and Applied Pharmacology, 2025)

Unraveling the impact of urban expansion on vegetation carbon sequestration capacity: A case study of the Yangtze River Economic Belt - Jinyang Wang; Zhenfeng Shao; Peng Fu; Qingwei Zhuang; Jiahui Chang; Peiqing Jing; Zhiyu Zhao; Zhenpeng Xu; Siyuan Wang; Fei Yang (Sustainable Cities and Society, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

A deep data fusion-based reconstruction of water index time series for intermittent rivers and ephemeral streams monitoring - Junyuan Fei; Xuan Zhang; Chong Li; Fanghua Hao; Yahui Guo; Yongshuo Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Triggering of a 2500-year coral shutdown in northern South China Sea by coupled East Asian Monsoon and El Niño–Southern Oscillation - Fei Tan; Yunfeng Zhang; Guowei Fu; Qi Shi; Xiyang Zhang; Shengnan Zhou; Mingzhuang Wang; Guotao Zhang; Xiaoju Liu; Jian-xin Zhao; Hongqiang Yang (Global and Planetary Change, 2025)

Mitigating frost heave of a soil stabilized with sisal fiber exposed to freeze-thaw cycles - Fei Deng; Jianguo Lu; Xusheng Wan; Boshi Liu; Binlong Zhang; Hao Fu (Geotextiles and Geomembranes, 2025)

High sensitivity and fast response wireless humidity sensor enabled by MXene-Lys for finger proximity detection and health monitoring applications - Jianing Kang; Feng Gao; Ying Wang; Jinghuan Fu; Siyuan Song; Fei Jin; Gongxun Bai; Changyu Shen (Chemical Engineering Journal, 2025)

Unraveling the role of oxygen vacancies in enhancing the SO2-resistance of α-MnO2 towards elemental mercury removal - Qian Yu; Fei Lai; Shiwei Sheng; Yujia Wang; Bo Yuan; Dong Fu (Chemical Engineering Journal, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

Agricultural Drought Vulnerability in the Middle Reaches of Yangtze River Basin under Environmental Change - Peng Yang; Fei Xu; Jun Xia; Jiang Li; Libo Zhou; Cai Fu (Journal of Earth Science, 2025)

Hydrochemical characteristics and evolution of geothermal waters in western Yunnan, China based on self-organizing map and hydrogeochemical simulation - Bo Li; Guangcai Wang; Fei Liu; Zheming Shi; Qingmin Kong; Shouchuan Zhang; Xin Yan; Fu Liao; Liang Guo; Chenglong Liu (Applied Geochemistry, 2025)

Whole-genome re-sequencing reveals genetic structure and selection signals of different populations in Megalobrama amblycephala - Shi-Long Wang; Li-Fei Luo; Yue Yu; Yu-Ye Fu; Ze-Xia Gao (Aquaculture, 2025)

Exploring the spatial heterogeneity of soil organic carbon and the influence of coastal factors: A case study in the Yellow River Delta, China - Youxiao Wang; Yingjun Sun; Qi Wang; Pingjie Fu; Yaohui Liu; Fang Wang; Fei Meng (Science of The Total Environment, 2025)

How Rhodococcus ruber accelerated biodegradation of benzophenone-3 - Fei Liu; Yue Ma; Wenxuan Li; Jue Cai; Haiyun Zhang; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Hazardous Materials, 2025)

Improvement of photosynthesis efficiency of Chlorella vulgaris by co culture with Bacillus licheniformis - Jia Li; Jinjin Wang; Ziqi Wang; Maorun Fu; Handong Zhao; Chen Chen; Fei Sun; Wenxiao Jiao (Food Bioscience, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Green synthesis and performance of micro-mesoporous ZSM-5/Y composite zeolite with hierarchical pore structure for vacuum gas oil (VGO) catalytic cracking - Fei Wang; Yaxuan Xie; Yuxiang Liu; Yuchao Lyu; Jianye Fu; Lishuang Ma; Xinmei Liu (Chemical Engineering Journal, 2025)

Redox photocatalysis CuFe-BTC for nitrate reduction and formaldehyde oxidation - Xu Huang; Kaiyin Wu; Fei Yang; Ruiyi Fu; Yunfei Ji; Wei Kong; Chao Su; Beibei Xiao (Chemical Engineering Journal, 2025)

Cross-equatorial extension of the Pacific-South American wave train enabled by Southeastern South American rainfall - Siyu Zhao; Rong Fu; Sen Zhao; Fei-Fei Jin; Hui Wang (Climate Dynamics, 2025)
The Pacific–South American (PSA) pattern is a key mode of climate variability in the mid-to-high latitudes of the Southern Hemisphere, impacting circulation and rainfall anomalies over South America. However, the effect of South American rainfall on the PSA has not been previously explored. This study focuses on the impact of rainfall over southeastern South American (SESA) during the austral summer (December–February). Observational analyses reveal that the PSA pattern remains confined to higher southern latitudes when SESA rainfall anomalies are weak. In contrast, strong SESA rainfall anomalies can generate a quasi-stationary Rossby wave train, which represents a cross-equatorial extension of the PSA. This wave train propagates along a southwest–northeast great circle path from higher latitudes, crosses the equator, and reaches the tropical Atlantic, southern Europe, and northern Africa, inducing a wet and cool weather condition over western and southern Europe. The observed wave train can be reproduced by the linear baroclinic model (LBM) simulations. Given the PSA’s connection to tropical forcing over the central Pacific, we examine differences in the wave response to central Pacific forcing alone versus combined central Pacific and SESA forcings. By incorporating SESA forcing, the wave train originally triggered by central Pacific forcing is amplified and extended. Our findings confirm the significant role of SESA rainfall anomalies in extending the PSA pattern to the Northern Hemisphere and highlight the South American continent as a land bridge that links circulation anomalies across the Pacific and Atlantic Oceans and the Southern and Northern Hemispheres.

Failure mechanism of toppling in anti-dip layered rock slope: a case study of the Xiangpingshan landslide in southwest China - Changkui Wang; Leilei Jin; Wenxi Fu; Fei Ye; Rui Qian; Guangchao Lv; Shuang Yao (Bulletin of Engineering Geology and the Environment, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Direct antifungal activity of methyl salicylate on soft rot caused by Rhizopus stolonifer and its membrane targeting mechanism - Liu Qianqian; Chen Qingmin; Liu Hu; Du Yamin; Jiao Wenxiao; Sun Fei; Fu Maorun; Tian Subo; Xin Xiaofei (Postharvest Biology and Technology, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

A sustainable machining method with high efficiency, high quality and low wear - electric arc electrochemical composite machining - Shengsheng Zhang; Jianping Zhou; Yinan Zhao; Guoyu Hu; Fei Fu; Lizhong Wang; Yan Xu (Journal of Cleaner Production, 2024)

Numerical investigation of the thermal hydrofracturing behavior of the Callovo-Oxfordian claystone - Carlos Plúa; Minh-Ngoc Vu; Gilles Armand; Zady Ouraga; Zhan Yu; Jian-Fu Shao; Qianyun Wang; Hua Shao; Tsubasa Sasaki; Sangcheol Yoon; Jonny Rutqvist; Fei Song; et al. (Geomechanics for Energy and the Environment, 2024)

Polygonati Rhizoma varieties and origins traceability based on multivariate data fusion combined with an artificial intelligence classification algorithm - Peng Chen; Chenghao Fei; Rao Fu; Xiaoyan Xiao; Yuwen Qin; Xiaoman Li; Zhijun Guo; Jianmin Huang; De Ji; Lin Li; Tulin Lu; Qiaosheng Guo; et al. (Food Chemistry, 2024)

Based on whole genome sequencing and metabolomics analysis the safety and probiotic characteristics of Lacticaseibacillus paracasei 36 isolated from Chinese fermented vegetables - Fei Wang; Xiang Li; Qi Wang; Qian Jin; Aikun Fu; Qiao Zhang; Rongchang Yang; Bin Deng; Weifen Li (Food Bioscience, 2024)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

Stable carbon isotope reveals high impact of fishing ship activities on total carbon from PM2.5 in Qingdao, China - Yao Wang; Hong-Wei Xiao; Mei-Ju Yin; Qi-Bin Sun; Fei Fu; Ji-Hua Tao; Hua-Yun Xiao (Environmental Pollution, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Whether hypoxia tolerance improved after short-term fasting is closely related to phylogeny but not to foraging mode in freshwater fish species - Ke-Ren Huang; Qian-Ying Liu; Yong-Fei Zhang; Yu-Lian Luo; Cheng Fu; Xu Pang; Shi-Jian Fu (Journal of Comparative Physiology B, 2024)

Improved method for quantitative fault sealing evaluation in sand-clay sequences: A case study from the west subsag of Bozhong Sag in the Bohai Bay basin, China - Xianqiang Song; Xiaofei Fu; Huiyong Li; Haixue Wang; Zhida Liu; Peng Xu; Fei Jiang; Zhaohan Xie (Marine and Petroleum Geology, 2024)

Size-resolved gas-particle partitioning of polycyclic aromatic hydrocarbons in a large temperature range of 50 ℃ - De-Qi Wang; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

A novel method for evaluating stability and mechanism of flexural toppling based on energy conservation principle and numerical simulation - Leilei Jin; Wenxi Fu; Yang Wang; Qianfeng Xiao; Yajing Li; Fei Ye (International Journal of Rock Mechanics and Mining Sciences, 2024)

Rosa roxburghii Tratt (Cili) has a more effective capacity in alleviating DSS-induced colitis compared to Vitamin C through B cell receptor pathway - Xiang Li; Qi Wang; Fei Wang; Qian Jin; Bin Deng; RongChang Yang; Aikun Fu; Fuyong Li; Qiao Zhang; Weifen Li (Food Research International, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

A novel efficient flame-retardant curing agent for epoxy resin based on P-N synergistic effect: Bio-based benzoxazine phosphate ester - Xuan Zhou; Rongzhi Li; Fei Fu; Minggui Shen; Qiaoguang Li; He Liu; Xu Xu; Zhanqian Song (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Genomic characteristics of human respiratory syncytial virus from children in China during 2017-2020 - Fei Li; Yun Zhu; Qiuping Li; Xiaolei Guan; Hailin Zhang; Changchong Li; Meng Zhang; Lei Li; Yiliang Fu; Yali Duan; Luci Huang; Zhengde Xie; et al. (Archives of Virology, 2024)

A hydro-mechanical closed form solution for the minimum safety thickness of water‑resistant rock in a karst tunnel under drag force in the connected fracture - Rui Qian; Qianqi Zhang; Qianfeng Xiao; Wenxi Fu; Guangchao Lv; Fei Ye (Tunnelling and Underground Space Technology, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Marine heatwaves alter competition between the cultured macroalga Gracilariopsis lemaneiformis and the harmful bloom alga Skeletonema costatum - Lin Gao; Yonglong Xiong; Fei-Xue Fu; David A. Hutchins; Kunshan Gao; Guang Gao (Science of The Total Environment, 2024)

Trend and inter-annual variability in regional climate models – Validation and hydrological implications in southeast Australia - Jin Teng; James C. Bennett; Steve Charles; Francis Chiew; Fei Ji; Nick Potter; Guobin Fu; Marcus Thatcher; Tomas Remenyi (Journal of Hydrology, 2024)

Magnetic modification of cerium organic frame materials to improve the phosphorus adsorption performance: Modulating the valence state - Boda Ouyang; Fei Li; Zhiyong Zhang; Xiaoyi Xie; Lei Chen; Wenjie Sun; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2024)

Greenhouse gas emissions during the rice season are reduced by a low soil C:N ratio using different upland-paddy rotation systems - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Chunlian Jin; Wenwen Song; Fei Deng; Xiaolong Lei; Youfeng Tao; et al. (Field Crops Research, 2024)

Structural design of cellulose-hyperbranched double-network for enhanced intramolecular diffusion kinetics of heavy metal ion capture processes - Jun Mao; Xianlin Lei; Xiyao Fu; Zhiping Chen; Hongxiang Zhu; Fei Xue; Zihan Yu; Lei Wang; Nannan Xia; Hui He (Chemical Engineering Journal, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Nervonic acid and its sphingolipids: Biological functions and potential food applications - Nghi Van Phung; Fei Rong; Wan Yue Xia; Yong Fan; Xian Yu Li; Shi An Wang; Fu Li Li (Critical Reviews in Food Science and Nutrition, 2024)

Numerical Simulation and On-Site Measurement of Dynamic Response of Flexible Marine Aquaculture Cages - Xiaoying Zhang; Fei Fu; Jun Guo; Hao Qin; Qian Sun; Zhe Hu (Journal of Marine Science and Engineering, 2024)
Flexible cages are widely used in marine aquaculture, yet their mechanical features in extreme seas are still unclear. This study proposes a numerical algorithm to solve the coupled response of the multiple cage systems. The net and mooring lines are modeled using the lumped-mass model, while the flexible floating collar system is assessed with the large-deformation FEM model, and the two models are coupled through an iterative scheme. Sea trials are conducted, and the motion of the cage is obtained using an image processing technique, which validates the numerical algorithm. Using the proposed numerical algorithm, a series of simulations are performed to investigate the response of flexible cages in extreme seas. Motions, line tensions, and structural sectional forces are studied, and the effects of factors such as the wavelength of incident waves and the diameter of collar pipes are investigated.

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Ferrocenedicarboxylate modified Bi-MOF for water decontamination via different advanced oxidation processes: Multifunction, mechanisms and biotoxicity test - Ya Gao; Fei Wang; Jie Tang; Chong-Chen Wang; Xiao-Hong Yi; Yuwei Wei; Guangchi Liu; Peng Wang; Huifen Fu; Chen Zhao; Xuchun Qiu; Shouliang Yi (Chemical Engineering Journal, 2024)

Corrigendum to ““One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection” [Chem. Eng. J. 457 (2023) 140997] - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Dissolved Organic Matters, an Intermediary of the Microbial Community and Potassium Fertilizers in A. carmichaeli rhizosphere Soil - Fei Xia; Meng Fu; Chen Liu; Yulong Li; Yi Qiang; Ding He; Guoyan Zhang; Langjun Cui (Journal of Soil Science and Plant Nutrition, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Evolution of volcanic activity and its impact on continental weathering, paleoproductivity, and runoff during the early Aptian in southern Tibet (eastern Tethys): Implications for regional to global environmental perturbations - Ying Nie; Xiugen Fu; Ahmed Mansour; Shengqiang Zeng; Mohamed S. Ahmed; Fangzhi Hu; Fei Lin; Zhe Qi; Qiangwang Wu; Manuel Rigo (Sedimentary Geology, 2024)

ε-Polylysine treatment maintains sensory quality, texture, flavor, and inhibits aerobic bacteria growth in vacuum-packed fresh-cut lettuce - Liu Qianqian; Zhang Xin; Han Cong; Chen Qingmin; Sun Fei; Fu Maorun; Zhao Handong; Xiao Zhijian; Tang Zheng (Postharvest Biology and Technology, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Are cretaceous intermediate–mafic igneous rocks from the northern South China Sea indicative of the slab rollback of the Paleo-Pacific Plate? - Ling Zhong; Ming-Cai Hou; Fei Wang; Ying Xia; Fu-Hao Xiong; Hai-Yang Cao (Lithos, 2024)

Developmental toxicity of the neonicotinoid pesticide clothianidin to the larvae of the crustacean Decapoda, Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Journal of Hazardous Materials, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Research on Sea Trial Techniques for Motion Responses of HDPE Floating Rafts Used in Aquaculture - Fei Fu; Xiaoying Zhang; Zhe Hu; Yan Li; Lihe Wang; Jianxing Yu (Journal of Marine Science and Engineering, 2024)
The innovative aquaculture equipment known as high-density polyethylene (HDPE) floating rafts has gained popularity among fishermen in the southeast coastal regions of China. Compared to deep-water anti-wave fish cages, the construction costs of HDPE floating rafts are 50% to 75% less. There is a dearth of comprehensive publicly available records of HDPE floating rafts sea trial data, despite substantial numerical studies on the motion response of aquaculture fish cages and scale model experiments under controlled-wave conditions. This study involves sea trial techniques under operational and extreme environmental conditions for motion responses of HDPE floating rafts, presents a comprehensive procedure for sea trials of HDPE floating rafts, summarizes the issues encountered during the trials, and suggests solutions. Using MATLAB for independent programming, motion videos and photos collected from the sea trials are processed for image capture, yielding the original time history curve of vertical displacement. Based on the sea trials’ data, including motion displacement, acceleration, mooring line force, overall deformation patterns, and current and wave data, recommendations are provided for the design and layout of HDPE floating rafts. Based on the Fast Fourier Transform (FFT) method for spectral analysis, the influence of interference items on the observational data is eliminated; the rationality of the observational data is verified in conjunction with the results of the Gabor Transform. This study offers a scientific analytical method for the structural design and safe operation of HDPE floating rafts and provides a reference for subsequent numerical simulations.

Molecular characterization and expression profile of the ALDH1A1 gene and its functions in yak luteal cells - Xixi Fei; Yanjin Zhu; Bangting Pan; Yuying Cheng; Qinhui Yang; Yumian Xie; Yan Xiong; Wei Fu; Xianrong Xiong; Jian Li (Theriogenology, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Two different types of hydrolases co-degrade ochratoxin A in a highly efficient degradation strain Lysobacter sp. CW239 - Xiaojie Fu; Qingru Fei; Xuanjun Zhang; Na Li; Liang Zhang; Yu Zhou (Journal of Hazardous Materials, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Characterization of an agmatine N-acetyltransferase from Bactrocera dorsalis that modulates ovary development - Fei-yue Teng; Ji-mei Feng; Fu-cai Ma; Zhuo-xin Wang; Yong-yue Lu; Yi-xiang Qi (Insect Biochemistry and Molecular Biology, 2024)

Study on multiscale structures and digestibility of cassava starch and medium-chain fatty acids complexes using molecular simulation techniques - Wenting Shang; Xin Li; Jinyu Du; Yuxin Guo; Dekun Fu; Yanfu He; Fei Pan; Weimin Zhang; Zhongkai Zhou (Food Research International, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Weak geostrophic wind driven ventilation in street canyons with trees and green walls: Cooperating or opposing dispersions of airborne pollutants? - Yu-Fei Tang; Hao Chen; Ming Yang; Zhi-Cheng Tan; Fu-Yun Zhao; Jiang-Hua Guo; Yueping Fang (Building and Environment, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

An analytical solution to predict slip-buckling failure of bedding rock slopes under the influence of top loading and earthquakes: Case studies of Hejia landslide and Tangjiashan landslide - Leilei Jin; Guanghong Ju; Zhengfeng Chen; Qianfeng Xiao; Wenxi Fu; Fei Ye; Yufeng Wei (Landslides, 2024)

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Next-generation neonicotinoid: The impact of cycloxaprid on the crustacean decapod Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Chemosphere, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Sulfur enhances iron plaque formation and stress resistance to reduce the transfer of Cd and As in the soil-rice system - Fei Miao; Xin Zhang; Qingling Fu; Hongqing Hu; Md. Shoffikul Islam; Linchuan Fang; Jun Zhu (Science of The Total Environment, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Novel (2,6-difluorobenzoyl)urea-activated fluorescent probe for fluorine-containing-pesticide detection - Yulong Liu; Fang Sun; Binbin Jia; Zishi Wang; Mingli Yue; Liu Yang; Ying Fu; Fei Ye (Journal of Environmental Chemical Engineering, 2024)

Dual-role KCl-assisted fabrication of porous carbon with controllable architecture from coal liquefaction residue for supercapacitors - Xiaoxia Yang; Guoxiao Sun; Fei Wang; Long Chen; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Feng Fu; Ru’an Chi (Fuel, 2024)

Optimizing BP neural network algorithm for Pericarpium Citri Reticulatae (Chenpi) origin traceability based on computer vision and ultra-fast gas-phase electronic nose data fusion - Peng Chen; Rao Fu; Yabo Shi; Chang Liu; Chenlu Yang; Yong Su; Tulin Lu; Peina Zhou; Weitong He; Qiaosheng Guo; Chenghao Fei (Food Chemistry, 2024)

Vertically aligned and conformal BN-coated carbon fiber to achieve enhanced thermal conductivity and electrical insulation of a thermal interface material - Min Huang; Zhiqian Wang; Nizao Kong; Biao Li; Chong Ye; Kun Jia; Liqin Fu; Yexin Tian; Donghong Wang; Fei Han (Chemical Engineering Journal, 2024)

Ca-based hybrid interfaces inhibit uncontrolled electrolyte decomposition for efficient Ion-Storage - Weihua Guo; Danchen Fu; Fei Tian; Huawei Song; Chengxin Wang (Chemical Engineering Journal, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Identification of volatile compounds and their bioactivities from unpolar fraction of Alpinia oxyphylla Miq. and mining key genes of nootkatone biosynthesis - Fapetu Kemi Busayo; Jin-Ling Yang; Xu-Po Ding; Ya-Li Wang; Cui-Juan Gai; Fei Wu; Hao-Fu Dai; Wen-Li Mei; Hui-Qin Chen (Natural Product Research, 2024)

Pilot-scale membrane-covered composting of food waste: Initial moisture, mature compost addition, aeration time and rate - Fei Wang; Ting Pan; Dafang Fu; Ioannis A. Fotidis; Christina Moulogianni; Yixin Yan; Rajendra Prasad Singh (Science of The Total Environment, 2024)

Exposure to heavy metallic and trace essential elements and risk of diminished ovarian reserve in reproductive age women: A case-control study - Tian Tian; Zheng Wang; Fang Liu; Yu Fu; Fei Kong; Yuanyuan Wang; Qin Li; Xiaoyu Long; Jie Qiao (Journal of Hazardous Materials, 2024)

Sulphur evolution in acidic and alkaline geothermal water related to magma in the Rehai geothermal field in the southeastern Tibet Plateau based on stable hydrogen, oxygen, sulphur isotopes - Bo Li; Qingmin Kong; Fu Liao; Guangcai Wang; Fei Liu; Liang Guo; Chenglong Liu; Zheming Shi (Geothermics, 2024)

A comprehensive review of biodetoxification of trichothecenes: Mechanisms, limitations and novel strategies - Yue Qiu; Jiaping Yan; Aodong Yue; Zhongchao Lu; Jianzhuang Tan; Hong Guo; Yuting Ding; Fei Lyu; Yan Fu (Food Research International, 2024)

Efficient detection of flusilazole by an electrochemical sensor derived from MOF MIL-53(Fe) for food safety - Yu-Han Sun; Liu Yang; Xian-Xian Ji; Yuan-Zhen Wang; Yu-Long Liu; Ying Fu; Fei Ye (Food Chemistry, 2024)

Rational design of a rapidly responsive and highly selective fluorescent probe for SO2 derivatives detection and imaging - Shiyi Zhang; Xiaopeng Yang; Ying Xu; Haiyang Wang; Fei Luo; Guangming Fu; Dingwei Yan; Miao Lai; Yu Ke; Yong Ye; Xiaoming Ji (Food Chemistry, 2024)

Effect of different bulking agents on fed-batch composting and microbial community profile - Fei Wang; Jingyao Wang; Yuheng He; Yixin Yan; Dafang Fu; Eldon R. Rene; Rajendra Prasad Singh (Environmental Research, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Photocatalytic depolymerization of lignin to produce high value-added chemicals by carbon quantum dots modified WO3 nanosheets - Zhijie Jiang; Xutang Liu; Wei Zhao; Fei Wang; Mingyu Cui; Linyang Dong; Chong Liang; Dingkai Wang; Shuiyuan Fu (Journal of Environmental Chemical Engineering, 2024)

External electricity-powered FeS/graphene/bacterial hybrid for Cr6+ removal from water lacking organic electron donors - Qi Zhu; Fei Feng; Zhong-er Long; Yunhong Huang; Haiyan Ni; Xueqin Fu; Longhai Dai; Long Zou (Journal of Environmental Chemical Engineering, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

An upcycling bioprocess for sustainable aviation fuel production from food waste-derived greenhouse gases: Life cycle assessment and techno-economic analysis - Chenyue Zhang; Rongzhan Fu; Lixia Kang; Yingqun Ma; Daidi Fan; Qiang Fei (Chemical Engineering Journal, 2024)

A Proactive Intervention Study in Metabolic Syndrome High-Risk Populations Using Phenome-Based Actionable P4 Medicine Strategy - Qiongrong Huang; Zhiyuan Hu; Qiwen Zheng; Xuemei Mao; Wenxi Lv; Fei Wu; Dapeng Fu; Cuihong Lu; Changqing Zeng; Fei Wang; Qiang Zeng; Qiaojun Fang; et al. (Phenomics, 2024)

Correction to: Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

A novel method for multi-pollutant monitoring in water supply systems using chemical machine vision - Jiacong Yan; Jianchao Lee; Lu Liu; Qiannan Duan; Jingzheng Lei; Zhizhi Fu; Chi Zhou; WeiDong Wu; Fei Wang (Environmental Science and Pollution Research, 2024)

Toxic effects of microplastics and nitrite exposure on intestinal histology, digestion, immunity, and microbial community of shrimp Litopenaeus vannamei - Yi-fu Xing; Xuan-yi Zhu; Jian-hua Huang; Yu-xiu Nan; Ya-fei Duan; Jia-song Zhang (Marine Pollution Bulletin, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

High organic aerosol in the low layer over a rural site in the North China Plain (NCP): Observations based on large tethered balloon - Jiannong Quan; Juntao Huo; Chenglong Zhang; Yubing Pan; Pengkun Ma; Zhiheng Liao; Zhigang Cheng; Xingcan Jia; Qianqian Wang; Qingyan Fu; Yujing Mu; Fei Hu (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Genomic and epigenetic characterization of the arsenic-induced oncogenic microRNA-21 - Haoyan Ji; Zhuoyue Bi; Aashna S. Pawar; Akimasa Seno; Bandar Saeed Almutairy; Yao Fu; Yiran Qiu; Wenxuan Zhang; Ziwei Wang; Chitra Thakur; Hongjuan Cui; Liqun Yang; et al. (Environmental Pollution, 2024)

High strength, self-healing and hydrophobic fully bio-based polybenzoxazine reinforced pine oleoresin-based vitrimer and its application in carbon fiber reinforced polymers - Xuan Zhou; Minggui Shen; Fei Fu; Qiaoguang Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2024)

αExtractor: a system for automatic extraction of chemical information from biomedical literature - Jiacheng Xiong; Xiaohong Liu; Zhaojun Li; Hongzhong Xiao; Guangchao Wang; Zhenjiang Niu; Chaoyuan Fei; Feisheng Zhong; Gang Wang; Wei Zhang; Zunyun Fu; Zhiguo Liu; et al. (Science China Life Sciences, 2024)

Effect evaluation of different green wastes on food waste digestate composting and improvement of operational conditions - Fei Wang; Yangtianrui Kang; Dafang Fu; Rajendra Prasad Singh (Environmental Science and Pollution Research, 2024)

Predicting land use change around railway stations: An enhanced CA-Markov model - Fei Fu; Xia Jia; Qiuji Zhao; Fangzhou Tian; Dong Wei; Ya Zhao; Yingzi Zhang; Jian Zhang; Xia Hu; Linchuan Yang (Sustainable Cities and Society, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Effect of reactor temperature and feeding ratio on fed-batch composting of household food waste and green wastes - Fei Wang; Chen Chen; Dafang Fu; Rajendra Prasad Singh (Biomass and Bioenergy, 2024)

Study on the Characteristics of Ecological Network and Critical Areas of Ecological Restoration in Hebei-Tianjin Coastal Wetlands - Feng Wang; Hui Gao; Jintong Liu; Tonggang Fu; Fei Qi; Yue Gao; Liang Zhao (Wetlands, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Dynamic Effect of Landslides Triggered by Earthquake: A Case Study in Moxi Town of Luding County, China - Hongfu Zhou; Fei Ye; Wenxi Fu; Bin Liu; Tian Fang; Rui Li (Journal of Earth Science, 2024)

Establishment of CRISPR-Cas-based antiparasitic agents for the swimming crab parasite Mesanophrys sp. - Xiaopeng Wang; Yueyue Zhou; Yingchao Zhang; Xiaofen Song; Ce Shi; Yuanyuan Fu; Lei Liu; Changkao Mu; Fei Yin; Weiwei Song; Chunlin Wang (Aquaculture, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Research on flow field characteristics in the karst tunnel face drilling hole (conduit) under the coupling between turbulence and seepage - Shuai Zhang; Danqing Song; Fei Ye; Wenxi Fu; Bin Zhang; Qianfeng Xiao (Tunnelling and Underground Space Technology, 2024)

Surface and subsurface runoff generation processes and their influencing factors on a hillslope in northern China - Tonggang Fu; Jintong Liu; Hui Gao; Fei Qi; Feng Wang; Mei Zhang (Science of The Total Environment, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Spatially heterogeneous shifts in vegetation phenology induced by climate change threaten the integrity of the avian migration network - Jie Wei; Fei Xu; Ella F. Cole; Ben C. Sheldon; Willem F. de Boer; Ben Wielstra; Haohuan Fu; Peng Gong; Yali Si (Global Change Biology, 2024)
Phenological responses to climate change frequently vary among trophic levels, which can result in increasing asynchrony between the peak energy requirements of consumers and the availability of resources. Migratory birds use multiple habitats with seasonal food resources along migration flyways. Spatially heterogeneous climate change could cause the phenology of food availability along the migration flyway to become desynchronized. Such heterogeneous shifts in food phenology could pose a challenge to migratory birds by reducing their opportunity for food availability along the migration path and consequently influencing their survival and reproduction. We develop a novel graph‐based approach to quantify this problem and deploy it to evaluate the condition of the heterogeneous shifts in vegetation phenology for 16 migratory herbivorous waterfowl species in Asia. We show that climate change‐induced heterogeneous shifts in vegetation phenology could cause a 12% loss of migration network integrity on average across all study species. Species that winter at relatively lower latitudes are subjected to a higher loss of integrity in their migration network. These findings highlight the susceptibility of migratory species to climate change. Our proposed methodological framework could be applied to migratory species in general to yield an accurate assessment of the exposure under climate change and help to identify actions for biodiversity conservation in the face of climate‐related risks.

Cloud characteristics over the Yunnan–Guizhou plateau as observed by MODIS and Himawari‐8 - Lu Yu; Xiaoyong Zhuge; Weihua Yuan; Ni Gao; Jian Li; Yunfei Fu; Fengjiao Chen; Bin Yao; Fei Tang; Wanlin Kan (International Journal of Climatology, 2023)
Cloud descriptions and parameterizations are major sources of uncertainty in weather and climate modelling studies. In this study, we investigated the cloud properties over the Yunnan–Guizhou Plateau (YGP) by using the Moderate Resolution Imaging Spectroradiometer (MODIS) and Himawari‐8 (H8_Japan and H8_Zhuge) cloud datasets. Corresponding to their distinct terrain features, the cloud climate patterns on the western and eastern sides of the YGP are different. Our results show that the spatial patterns of the cloud parameters in all three datasets are very similar over the YGP, especially the cloud cover and cloud effective radius. The high cloud frequency region is located to the east of Yunnan–Guizhou quasi‐stationary front in cold season, and the largest gradient is along front. On frontal days, the regional differences in the cloud properties over the YGP are much more obvious, with the cloud cover across the front increasing from ~20%–35% on its western side to more than 95% on its eastern side. Furthermore, higher thin clouds with larger cloud effective radius typically exist on the western side of the front, while lower thick clouds with smaller particles appear on its eastern side. This study enhances our understanding how cloud characteristics impact by the frontal system and provide a valuable insight for the design and improvement of cloud microphysics parameters in weather forecast models over the YGP region.

Tumor suppressive activity of AHR in environmental arsenic-induced carcinogenesis - Ziwei Wang; Yao Fu; Akimasa Seno; Zhuoyue Bi; Aashna S. Pawar; Haoyan Ji; Bandar Saeed Almutairy; Yiran Qiu; Wenxuan Zhang; Chitra Thakur; Fei Chen (Toxicology and Applied Pharmacology, 2023)

Free radical formation via BDE-209 thermolysis in the precalciner of a cement kiln: Simulation and DFT study - Jinzhong Yang; Bo-Tao Zhang; Lu Tian; Qingqi Die; Fei Wang; Haihui Fu; Yufei Yang; Qifei Huang (Science of The Total Environment, 2023)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Spatially resolved transcriptomics reveals distinct pulmonary immune responses during influenza virus and SARS-CoV-2 infections - Min Zhao; Fei Shao; Zhen Liu; Jiangwen Ma; Dou Yu; Hangjie Zhang; Lianpan Dai; Kun Xu; Xin Zhao; Mengli Zheng; George Fu Gao; Shuo Wang (Science Bulletin, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Component design optimization of green roof substrate layer based on the assessment of multifunctional performance - Yiming Fei; Dafang Fu; Chen Xu; Rajendra Prasad Singh (Environmental Research, 2023)

Mo isotopes record recycling of anoxic sediment in a Paleo-oceanic subduction zone - Xiang Fu; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Canagliflozin ameliorates high glucose-induced apoptosis in NRK-52E cells via inhibiting oxidative stress and activating AMPK/mTOR-mediated autophagy - Hong Liu; Weidong Chen; Sheng Wan; Ye Chen; Mengjing Fu; Zengsi Wang; Fei Xiong; Yanmin Zhang (Molecular Biology Reports, 2023)

The Influence of Meridional Variation in North Pacific Sea Surface Temperature Anomalies on the Arctic Stratospheric Polar Vortex - Tao Wang; Qiang Fu; Wenshou Tian; Hongwen Liu; Yifeng Peng; Fei Xie; Hongying Tian; Jiali Luo (Advances in Atmospheric Sciences, 2023)

Design, synthesis and biological activity determination of novel phenylpyrazole protoporphyrinogen oxidase inhibitor herbicides - Li-xia Zhao; Kun-yu Chen; Hua-yong Zhao; Yue-li Zou; Shuang Gao; Ying Fu; Fei Ye (Pesticide Biochemistry and Physiology, 2023)

Ophiolites and Earth's mantle ophiolites, podiform chromitites and deep mantle recycling - Paul T. Robinson; Mei-Fu Zhou; Jingsui Yang; Fahui Xiong; Peng-Fei Zhang (Lithos, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Evolution law and mechanism of time-delayed spalling in a deep TBM tunnel: A case study - Chen Fan; Xia-Ting Feng; Lianjie Fu; Jun Zhao; Chengxiang Yang; Zhibin Yao; Jun Wang; Fei Wei (Engineering Geology, 2023)

Renewable and efficient removal of arsenic from contaminated water by modified biochars derived from As-enriched plant - Mengxi Feng; Xin Zhang; Qingling Fu; Hongqing Hu; Fei Miao; Chaojun Huang; Jun Zhu (Bioresource Technology, 2023)

Maternal Kdm2a-mediated PI3K/Akt signaling and E-cadherin stimulate the morula-to-blastocyst transition revealing crucial roles in early embryonic development - Xianrong Xiong; Manzhen Yang; Zhuo Hai; Xixi Fei; Yanjin Zhu; Bangting Pan; Qinhui Yang; Yumian Xie; Yuying Cheng; Yan Xiong; Daoliang Lan; Wei Fu; et al. (Theriogenology, 2023)

Testis-specific knockout of Kdm2a reveals nonessential roles in male fertility but partially compromises spermatogenesis - Xianrong Xiong; Xiangyue Huang; Yanjin Zhu; Zhuo Hai; Xixi Fei; Bangting Pan; Qinhui Yang; Yan Xiong; Wei Fu; Daoliang Lan; Xiaojian Zhang; Jian Li (Theriogenology, 2023)

Precision engineering of precious metal catalysts for enhanced hydrogen production efficiency - Yao Tong; Hailing Ma; Fei Xiao; Sivasambu Bohm; Hongxin Fu; Yang Luo (Process Safety and Environmental Protection, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

Semiconductors modified gourd-shaped hollow PtNi and their directional electron and mass transfer effects - Fu-Fei Pu; Yu-Xuan Xiao; Xiong Yang; Fei Yu; Lei Xia; Jiang-Bo Chen; Lu Wu; Jing-Jing Xie; Wen-Ying Zhao; Yu Liu; Li-Ying Wang; Jie Ying; et al. (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Effects of size and surface charge on the sedimentation of nanoplastics in freshwater - Honglu Zhu; Xiaolei Fan; Hua Zou; Rong-Bo Guo; Shan-Fei Fu (Chemosphere, 2023)

A visual circuit related to the habenula mediates the prevention of cocaine relapse by bright light treatment - Yunwei Fu; Yan Yang; Lu Huang; Xiaodan Huang; Qian Yang; Qian Tao; Jijin Wu; Kwok-Fai So; Song Lin; Ti-Fei Yuan; Chaoran Ren (Science Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The Toarcian Oceanic Anoxic Event in a shelf environment (Eastern Tethys): Implications for weathering and redox conditions - Ying Nie; Xiugen Fu; Jintong Liang; Hengye Wei; Zhengan Chen; Fei Lin; Shengqiang Zeng; Yunhao Wu; Yi Zou; Ahmed Mansour (Sedimentary Geology, 2023)

Short-term effects of fine particulate matter constituents on mortality considering the mortality displacement in Zhejiang province, China - Jingqiao Fu; Fangrong Fei; Shiyi Wang; Qi Zhao; Xuchao Yang; Jieming Zhong; Kejia Hu (Journal of Hazardous Materials, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Gellan gum-based functional films integrated with bacterial cellulose and nano-TiO2/CuO improve the shelf life of fresh-cut pepper - Fei Chen; Xia Chang; Haishan Xu; Xincheng Fu; Shenghua Ding; Rongrong Wang (Food Packaging and Shelf Life, 2023)

Magnesium–oxygen isotope constraints on the origin of rodingites in oceanic lithosphere - Mei-Shan Zhao; Yi-Xiang Chen; Jia-Wei Xiong; Xin-Yue Qiao; Yong-Fei Zheng; Wen-Yong Duan; Fang Huang; Zi-Fu Zhao (Chemical Geology, 2023)

Insights into the reaction of anammox to exogenous pyridine: Long-term performance and micro mechanisms - Jie Qian; Di Luo; Peng-fei Yu; Bin Ye; Ying-hua Li; Yong-yong Wang; Yu-nan Gao; Jin-xiang Fu (Bioresource Technology, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Developing and characterizing monoclonal antibodies of Guertu bandavirus nucleoprotein for developing methods of Guertu bandavirus and severe fever with thrombocytopenia syndrome virus detection - Jin Qian; Liyan Fu; Xiaoli Wu; Zhiying Wang; Hualin Wang; Yan Zeng; Guirong Cheng; Fei Deng; Shu Shen (Brazilian Journal of Microbiology, 2023)

3-D transient electromagnetic inversion based on explicit finite-difference forward modeling - Fei Li; Qiang Tan; Lai-Fu Wen; Dan Huang (Applied Geophysics, 2023)

Decoupled local climate and chemical weathering intensity of fine-grained siliciclastic sediments from a paleo-megalake: An example from the Qaidam basin, northern Tibetan Plateau - Ling Wang; Xing Jian; Hanjing Fu; Wei Zhang; Fei Shang; Ling Fu (Sedimentary Geology, 2023)

Design, synthesis and biological activity of novel triketone herbicides containing natural product fragments - Zi-Bin Jiang; Shuang Gao; Wei Hu; Bo-Ren Sheng; Juan Shi; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

Antifungal pentachloronitrobenzene/hydroxypropyl-beta-cyclodextrin inclusion complex nanofibers by electrospun with no polymer: Fabrication and characterization - Shuang Gao; Lei Zong; Yuhang Zhang; Yang Zhang; Xinyu Guo; Guanhua Guo; Lixia Zhao; Fei Ye; Ying Fu (Journal of Cleaner Production, 2023)

Simulated upwelling and marine heatwave events promote similar growth rates but differential domoic acid toxicity in Pseudo-nitzschia australis - Kyla J. Kelly; Amjad Mansour; Chen Liang; Andrew M. Kim; Lily A. Mancini; Matthew J. Bertin; Bethany D. Jenkins; David A. Hutchins; Fei-Xue Fu (Harmful Algae, 2023)

Precursor Development of Sandstone Failure Using IR to Measure the Fractal Characteristics - Hai Sun; Hongyan Zhu; Changyan Shi; Fei Wang; Liqiang Ma; Chun Fu; Pengfei Cui; Yuanyuan Du (Geotechnical and Geological Engineering, 2023)

Health Risk Assessment of Organophosphate Flame Retardants in Soil Across China Based on Monte Carlo Simulation - Mei-Hong Chen; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Archives of Environmental Contamination and Toxicology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Sensitive fluorescence assay for the detection of glyphosate with NAC Cu2+ complex - Qiuhuan Liu; Shijie Li; Yujiong Wang; Liu Yang; Mingli Yue; Yulong Liu; Fei Ye; Ying Fu (Science of The Total Environment, 2023)

Response spectra for transient pore-pressure in a sandy seabed under random waves: Frequency-filtering effect - Jia-Hao Yu; Fu-Ping Gao; Chang-Fei Li (Ocean Engineering, 2023)

Fe-Si-C isotope constraints on the genesis of iron ores in Gongchangling iron deposit in northeastern China - Jian-Fei Fu; Jin-Peng Luan; San-shi Jia; Yin-Hua Luo; Jun-Dian Chen; Fu-Quan Zhao (Journal of Geochemical Exploration, 2023)

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Solar radiation utilization of five upland–paddy cropping systems in low-light regions promoted by diffuse radiation of paddy season - Qi Liu; Zhiping Yang; Wei Zhou; Tao Wang; Yong Fu; Xueping Yue; Hong Chen; Youfeng Tao; Fei Deng; Xiaolong Lei; Wanjun Ren; Yong Chen (Agricultural and Forest Meteorology, 2023)

Differences of functionalized graphene materials on inducing chronic aquatic toxicity through the regulation of DNA damage, metabolism and oxidative stress in Daphnia magna - Yang Huang; Hongye Yao; Xuehua Li; Fei Li; Xiaoqing Wang; Zhiqiang Fu; Ningjing Li; Jingwen Chen (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

The effect of vacancy defective Mg (0001) surface on hydrogenation of Ni-Mg-CNTs: A mechanistic investigation - Congwen Duan; Mengmeng Wu; Xinya Wang; Dong Fu; Yuling Zhang; Wei Lv; Lianxi Hu; Ming Li; Fei Wang; Ying Wu (Fuel, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Molybdenum isotopes record recycling of subducting sediment in active continental margin, Northeast China - Wei Fang; Li-Qun Dai; Xiang Fu; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Airflow Mitigation and Pollutant Purification in an Idealized Urban Street Canyon with Wind Driven Natural Ventilation: Cooperating and Opposing Effects of Roadside Tree Plantings and Non-uniform Building Heights - Yu-Fei Tang; Ya-Bing Wen; Hao Chen; Zhi-Cheng Tan; Yi-He Yao; Fu-Yun Zhao (Sustainable Cities and Society, 2023)

Response of microbial taxonomic and nitrogen functional attributes to elevated nitrate in suburban groundwater - Ling-Zhi Zhang; Wei He; Fu-Yi Huang; Wei He; Pengpeng Zhou; Cuibai Chen; Christopher Rensing; Kristian Koefoed Brandt; Jiangtao He; Fei Liu; Yi Zhao; Huaming Guo (Science of The Total Environment, 2023)

Discovery of novel HPPD inhibitors: Virtual screening, molecular design, structure modification and biological evaluation - Xin-Yu Leng; Shuang Gao; Yi-Fan Ma; Li-Xia Zhao; Meng Wang; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

Fluid evolution and ore genesis of the A'gui Cu deposit in southern Great Xing'an Range, Northeast China: Evidence from fluid inclusion and C–H–O–S–Pb isotopes - Xue Wang; Ke-yong Wang; Li-juan Fu; Qing-ying Zhao; Qing-fei Sun; Chao Zhang (Geochemistry, 2023)

Experimental and simulation study on hydroxyl group promoting low-temperature oxidation of active groups in coal - Xun Zhang; Bing Lu; Jing Zhang; Xiang Fu; Hanzhong Deng; Ling Qiao; Cong Ding; Fei Gao (Fuel, 2023)

Fabrication strategies of metal–organic frameworks derivatives for catalytic aqueous pollutants elimination - Fei Wang; Ya Gao; Shan-Shan Liu; Xiao-Hong Yi; Chong-Chen Wang; Huifen Fu (Chemical Engineering Journal, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Temporal geochemical variation in early Paleozoic mafic rocks from the Qinling orogen: Implications for the evolution of slab fluids during oceanic subduction - Hai-Yang Yan; Guo-Chao Sun; Zi-Fu Zhao; Li-Qun Dai; Fei Zheng (Chemical Geology, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Removal of Tetracycline Hydrochloride by Ball-Milled Mulberry Biochar - Zhongpu Yu; Licheng Ji; Yihan Zuo; Feiyan Zhang; Chengcheng Wei; Fei Jiang; Xianju Fu; Wenge Wu; Jian Du; Chengxia Chen; Feiyue Li (Water, Air, & Soil Pollution, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

The LightGBM-based classification algorithm for Chinese characters speech imagery BCI system - Hongguang Pan; Zhuoyi Li; Chen Tian; Li Wang; Yunpeng Fu; Xuebin Qin; Fei Liu (Cognitive Neurodynamics, 2023)

Deep kimberlite prospecting and thrust-nappe structure: Analysis of diamond metallogenic belt in Wafangdian, China - Mishan Zhong; Guoren Zhang; Haitao Fu; Haipeng Wang; Zhenghong Liu; Jin Liu; ZiJie Wu; Fuliang Gao; Yongzhao Gao; Yuqi Pan; Fanglai Wan; Lei Yang; et al. (International Geology Review, 2023)

Comparison of the chronic and multigenerational toxicity of racemic glufosinate and -glufosinate to Caenorhabditis elegans at environmental concentrations - Xu Zhao; Kan Fu; Kai-ping Xiang; Lan-ying Wang; Yun-fei Zhang; Yan-ping Luo (Chemosphere, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Integrated effects of residual plastic films on soil-rhizosphere microbe-plant ecosystem - Fei Fu; Bibo Long; Qian Huang; Juanjuan Li; Weijun Zhou; Chong Yang (Journal of Hazardous Materials, 2023)

Evaluating main drivers of runoff changes across China from 1956 to 2000 by using different budyko-based elasticity methods - Jianyu Fu; Bingjun Liu; Weiguang Wang; Esther Xu Fei (Journal of Environmental Management, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

Ultrasonication significantly enhances grafting efficiency of chitosan-ferulic acid conjugate and improves its film properties under Fenton system - Haishan Xu; Xincheng Fu; Hui Kong; Fei Chen; Xia Chang; Zemin Ding; Rongrong Wang; Yang Shan; Shenghua Ding (Food Research International, 2023)

“One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2023)

Histone Deacetylation Modifier Induced One New Resorcylic Acid Lactone 7′(Z)-zeaenol from the Zoanthid-Derived Fungus Cochliobolus lunatus - Zhenkun Zhang; Jiaxiang Wang; Fei Cao; Xiaojian Zhou; Jingshuai Wu; Xiumei Fu; Min Chen; Changyun Wang (Journal of Ocean University of China, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Organic matter accumulation mechanism under global/regional warming: Insight from the Late Barremian calcareous shales in the Qiangtang Basin (Tibet) - Ying Nie; Xiugen Fu; Xianchuan Liu; Hengye Wei; Shengqiang Zeng; Fei Lin; Youli Wan; Chunyan Song (Journal of Asian Earth Sciences, 2023)

Selective luminescent sensing of teflubenzuron and oxyfluorfen by a resorcin[4]arene-based metal-organic framework - Bing-Bing Lu; Zhi-Xin Xing; Yong-Shun Bao; Fei Ye; Ying Fu (Chemical Engineering Journal, 2023)

Combined nonlinear wave and current induced instantaneously-liquefied soil depth in a non-cohesive seabed - Li-Jing Yang; Fu-Ping Gao; Chang-fei Li (Coastal Engineering, 2023)

Grapevine VaRPP13 protein enhances oomycetes resistance by activating SA signal pathway - Yuchen Chen; Wei Wu; Bohan Yang; Fei Xu; Shanshan Tian; Jiang Lu; Peining Fu (Plant Cell Reports, 2022)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

Mass movement of a long-runout catastrophic landslide on Aug. 21, 2020, in Hanyuan County of China - Xing-Yu Yuan; Zheng-Feng Chen; Wen-Xi Fu; Yue Liu; Hong-Fu Zhou; Fei Ye (Bulletin of Engineering Geology and the Environment, 2022)

Acute transcriptomic changes in murine RAW 264.7 cells following pseudorabies virus infection - Chao Tong; Peng-Fei Fu; Sheng-Li Ming; Lei Zeng; He-Shui Zhu; Jiang Wang (Archives of Virology, 2022)

Identification of nitrogen pollution sources and transport transformation processes in groundwater of different landforms using C, H, N, and O isotope techniques: an example from the lower Weihe River - Lei Duan; Yakun Wu; Jinghui Fan; Fei Ye; Chenchen Xie; Xinyi Fu; Yaqiao Sun (Environmental Science and Pollution Research, 2022)

The heterogeneous orogenic lithospheric mantle: whole rock and mineral geochemical evidence from early Paleozoic mafic intrusives in the Qilian orogen, China - Qi Chen; Li-Qun Dai; Zi-Fu Zhao; Yong-Fei Zheng; Yao Zhou (Contributions to Mineralogy and Petrology, 2022)

The recombinant subunit vaccine encapsulated by alginate‐chitosan microsphere enhances the immune effect against Micropterus salmoides rhabdovirus - Fei‐Fan Xu; Fu‐Yi Jiang; Guo‐Qing Zhou; Jun‐Yao Xia; Fei Yang; Bin Zhu (Journal of Fish Diseases, 2022)
The disease caused by Micropterus salmoides rhabdovirus (MSRV) has brought substantial economic losses to the largemouth bass aquaculture industry in China. Vaccination was considered as a potential way to prevent and control this disease. As a kind of sustained and controlled release system, alginate and chitosan microspheres (SA‐CS) are widely used in the development of oral vaccination for fish. Here, we prepared a king of alginate‐chitosan composite microsphere to encapsulate the second segment of MSRV glycoprotein (G2 protein) and then evaluated the immune effect of the microsphere vaccine on largemouth bass. Largemouth bass were vaccinated via intragastric immunization by different treatments (PBS, SA‐CS, G2 and SA‐CS‐G2). The results showed that a stronger immune response including serum antibody levels, immune‐related physiological indexes (acid phosphatase, alkaline phosphatase, superoxide dismutase and total antioxidant capacity) and the expression of immune‐related gene ( IgM、IL‐8、IL‐1β、CD4、TGF‐β、TNF‐α ) can be induced obviously with SA‐CS‐G2 groups compared with G2 groups when fish were vaccinated. Furthermore, fish were injected with a lethal dose of MSRV after immunization for 28 days, and the highest relative percentage survival (54.8%) was observed in SA‐CS‐G2 group (40 μg per fish), which is significantly higher than that of G2 group (25.8%). This study showed that alginate‐chitosan microspheres as the vaccine carrier can effectively improve the immune effect of oral vaccination and induce better immune protection effect against MSRV infection.

Coupled Thermo–Mechanical Damage Evolution of Granite under Repeated Heating–Cooling Cycles and the Applications of Mohr–Coulomb and Drucker–Prager Models - Jian Yang; Li-Yun Fu; Fei Wang; Wubing Deng (Natural Resources Research, 2022)

Temperature variability interacts with mean temperature to influence the predictability of microbial phenotypes - Fei‐Xue Fu; Bernhard Tschitschko; David A. Hutchins; Michaela E. Larsson; Kirralee G. Baker; Allison McInnes; Tim Kahlke; Arjun Verma; Shauna A. Murray; Martina A. Doblin (Global Change Biology, 2022)
Despite their relatively high thermal optima ( T opt ), tropical taxa may be particularly vulnerable to a rising baseline and increased temperature variation because they live in relatively stable temperatures closer to their T opt . We examined how microbial eukaryotes with differing thermal histories responded to temperature fluctuations of different amplitudes (0 control, ±2, ±4°C) around mean temperatures below or above their T opt . Cosmopolitan dinoflagellates were selected based on their distinct thermal traits and included two species of the same genus (tropical and temperate Coolia spp.), and two strains of the same species maintained at different temperatures for >500 generations (tropical Amphidinium massartii control temperature and high temperature, CT and HT, respectively). There was a universal decline in population growth rate under temperature fluctuations, but strains with narrower thermal niche breadth (temperate Coolia and HT) showed ~10% greater reduction in growth. At suboptimal mean temperatures, cells in the cool phase of the fluctuation stopped dividing, fixed less carbon (C) and had enlarged cell volumes that scaled positively with elemental C, N, and P and C:Chlorophyll‐ a . However, at a supra‐optimal mean temperature, fixed C was directed away from cell division and novel trait combinations developed, leading to greater phenotypic diversity. At the molecular level, heat‐shock proteins, and chaperones, in addition to transcripts involving genome rearrangements, were upregulated in CT and HT during the warm phase of the supra‐optimal fluctuation (30 ± 4°C), a stress response indicating protection. In contrast, the tropical Coolia species upregulated major energy pathways in the warm phase of its supra‐optimal fluctuation (25 ± 4°C), indicating a broadscale shift in metabolism. Our results demonstrate divergent effects between taxa and that temporal variability in environmental conditions interacts with changes in the thermal mean to mediate microbial responses to global change, with implications for biogeochemical cycling.

Effects of CYP24A1 polymorphisms on premature ejaculation: a case–control study - Fei Wang; Defan Luo; Jianxiang Chen; Cuiqing Pan; Zhongyao Wang; Housheng Fu; Jiangbing Xu; Meng Yang; Shaowei Mo; Liying Zhuang; Weifu Wang (Journal of Genetics, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Potential millennial‐scale avian declines by humans in southern China - Feng Dong; Qiang Zhang; Yi‐Lin Chen; Fu‐Min Lei; Shou‐Hsien Li; Fei Wu; Xiao‐Jun Yang (Global Change Biology, 2022)
Mounting observational records demonstrate human‐caused faunal decline in recent decades, while accumulating archaeological evidence suggests an early biodiversity impact of human activities during the Holocene. A fundamental question arises concerning whether modern wildlife population declines began during early human disturbance. Here, we performed a population genomic analysis of six common forest birds in East Asia to address this question. For five of them, demographic history inference based on 25–33 genomes of each species revealed dramatic population declines by 4‐ to 48‐fold over millennia (e.g. 2000–5000 thousand years ago). Nevertheless, summary statistics detected nonsignificant correlations between these population size trajectories and Holocene temperature variations, and ecological niche models explicitly predicted extensive range persistence during the Holocene, implying limited demographic consequence of Holocene climate change. Further analyses suggest high negative correlations between the reconstructed population declines and human disturbance intensities and indicate a potential driver of human activities. These findings provide a deep‐time and large‐scale insight into the recently recognized avifaunal decline and support an early origin hypothesis of human effects on biodiversity. Overall, our study sheds light on the current biodiversity crisis in the context of long‐term human–environment interactions and offers a multi‐evidential framework for quantitatively assessing the ecological consequences of human disturbance.

The activity, segmentation, and evolution characteristics of large-scale landslides along the Anninghe active fault zone, Southwest China - Hongfu Zhou; Fei Ye; Wenxi Fu; Yuting Wei; Yadong Qin; Wenqing Tang; Tian Fang (Bulletin of Engineering Geology and the Environment, 2022)

Wheat Ms2 confers complete male sterility without penalizing other traits - Huifei Zhang; Qunqun Hao; Fei Ni; Bo Lyu; Allan Caplan; Jiajie Wu; Daolin Fu (Cereal Research Communications, 2022)

Alteromonas oceanisediminis sp. nov., isolated from deep-sea sediment - Xiao-Yu Zhang; Zhen Wang; Jun-Hui Cheng; Hui-Hui Fu; Yu-Zhong Zhang; Xiu-Lan Chen; Xi-Ying Zhang; Xiao-Yan Song; Yu-Qiang Zhang; Fei Xu (Archives of Microbiology, 2022)

CFRP Strengthening and Rehabilitation of Inner Corroded Steel Pipelines under External Pressure - Jianxing Yu; Weipeng Xu; Yang Yu; Fei Fu; Huakun Wang; Shengbo Xu; Shibo Wu (Journal of Marine Science and Engineering, 2022)
The objective of this study was to investigate the performance of pipelines repaired with carbon-fibre-reinforced polymer (CFRP) under external pressure. The repaired pipeline experienced defects in terms of thinning of its local inner wall. The three-dimensional finite element method was used to analyse the collapse pressure of repaired pipes with internal corrosion defects. The traction–separation law and interlaminar damage criterion were applied to simulate the collapse process of repaired pipes. The results show that the collapse pressure of the composite-repaired pipe increased and the CFRP significantly reduced the strain in the defect region. It was observed that the ovality of the corrosion defect region was reduced and that the repair effectiveness mainly depended on the length, thickness, and interlayer cohesion.

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Ferroptosis inhibitory constituents from the fruits of Cullen corylifolium - Aftab Yaseen; Fan Yang; Xia Zhang; Fu Li; Bin Chen; Ahmed Hassan Ibrahim Faraag; Ming-Kui Wang; Xiao-Fei Shen; Lun Wang (Natural Product Research, 2021)

Identification of antibiotic resistance genes and associated mobile genetic elements in permafrost - Jian Cao; Fei Liu; Shuli Liu; Jun Wang; Baoli Zhu; Yi Shi; George Fu Gao (Science China Life Sciences, 2021)

Characterization of the novel hybrid cultivar E25 of Saccharina japonica in the northern farming region of China - Li Su; Ti Feng Shan; Jing Li; Su Qin Gao; Shao Jun Pang; Xiao Fei Leng; Yan Zhang; Ming Fu Zhang; Hong Tao Gao (Journal of Applied Phycology, 2021)

A novel BRET based genetic coded biosensor for apoptosis detection at deep tissue level in live animal - Yueling Zhang; Juan Hu; Meijuan Yu; Zhirong Wang; Hucheng Qing; Huheng Fu; Liudi Yuan; Fei Li; Sheng Zhao (Apoptosis, 2021)

Selection for low-cadmium cultivars and cadmium subcellular distribution comparison between two selected cultivars of eggplant (Solanum melongena L.) - Chuang Shen; Hui-Ling Fu; Qiong Liao; Bai-Fei Huang; Ying-Ying Huang; Jun-Liang Xin (Environmental Science and Pollution Research, 2021)

Comparative physiological and proteomic analyses of mangrove plant Kandelia obovata under cold stress - Jiao Fei; You-Shao Wang; Hao Cheng; Fu-Lin Sun; Cui-Ci Sun (Ecotoxicology, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

The “8·21” rainfall-induced Zhonghaicun landslide in Hanyuan County of China: surface features and genetic mechanisms - Fei Ye; Wen-Xi Fu; Hong-Fu Zhou; Yue Liu; Ren-Ji Ba; Shuang Zheng (Landslides, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Influence of surface cracks on temperature response of concrete under constant climate environment - Jian-Hua Jiang; Yong-Quan Fu; Fei-Fei Hu; Wei-Xin Weng (European Journal of Environmental and Civil Engineering, 2021)

Landslide distribution and sliding mode control along the Anninghe fault zone at the eastern edge of the Tibetan Plateau - Hong-fu Zhou; Bin Liu; Fei Ye; Wen-xi Fu; Wen-qing Tang; Ya-dong Qin; Tian Fang (Journal of Mountain Science, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Successful treatment of refractory pure red cell aplasia with eltrombopag after ABO-incompatible allogeneic hematopoietic stem cell transplantation - Yang Gao; Fei Gao; Jimin Shi; Huarui Fu; He Huang; Yanmin Zhao (Journal of Zhejiang University-SCIENCE B, 2021)

Deformation of the Zhangjiazhuang high-speed railway tunnel: an analysis of causal mechanisms using geomorphological surveys and D-InSAR monitoring - Xing-min Meng; Tian-jun Qi; Yan Zhao; Tom Dijkstra; Wei Shi; Yin-fei Luo; Yuan-zhao Wu; Xiao-jun Su; Fu-meng Zhao; Jin-hui Ma; Yi Zhang; Guan Chen; et al. (Journal of Mountain Science, 2021)

Interactions Between Ultraviolet B Radiation, Warming, and Changing Nitrogen Source May Reduce the Accumulation of Toxic Pseudo-nitzschia multiseries Biomass in Future Coastal Oceans - Kyla J. Kelly; Fei-Xue Fu; Xiaowen Jiang; He Li; Dong Xu; Nina Yang; Michelle A. DeMers; Joshua D. Kling; Kunshan Gao; Naihao Ye; David A. Hutchins (Frontiers in Marine Science, 2021)
Understanding the environmental conditions that trigger Pseudo-nitzschia bloom formation and domoic acid (DA) production is critical as the frequency and severity of these toxic blooms increases in the face of anthropogenic change. However, predicting the formation of these harmful blooms in a future ocean remains a challenge. Previous studies have examined the effects of single environmental drivers on Pseudo-nitzschia spp. growth and toxin production, but few have considered the interactions between them. In this multiple driver study with Pseudo-nitzschia multiseries , we used a full factorial matrix experimental design to examine the simultaneous effects of temperature (20 and 25°C), nitrogen source (nitrate and urea), and irradiance (photosynthetically active radiation with and without ultraviolet B radiation; UVB). This strain of P. multiseries was unable to withstand prolonged exposures (>0.5 h) to 0.06 mw⋅cm –2 UVB light, with implications for near-surface bloom formation if future shallower mixed layers increase UVB exposure. Growth rates were inhibited by UVB, but photosynthesis and carbon fixation continued at a reduced capacity. Additionally, DA synthesis continued despite UVB-induced growth inhibition. Warming by 5°C enhanced cellular DA quotas three-fold. Within these warmer treatments, urea-grown cultures exposed to UVB had the highest amount of DA per cell, suggesting that interactive effects between UVB exposure, warming, and urea can synergistically enhance toxin production. However, overall production of toxic biomass was low, as growth-integrated DA production rates were near zero. This indicates that although Pseudo-nitzschia multiseries cell-specific toxicity could worsen in an anthropogenically-altered future ocean, bloom formation may be inhibited by increased exposure to UVB. This multi-variable experimental approach revealed previously unknown interactions that could not have been predicted based on combined effects of single-variable experiments. Although P. multiseries DA production may be enhanced in a future ocean, inherent sensitivity to prolonged UVB exposure may moderate trophic transfer of toxin to coastal food webs.

A female carrier of a novel DMD mutation with slightly skewed X-chromosome inactivation shows a suspected case of Becker muscular dystrophy in a Chinese family - Jianfan Chen; Hui Zheng; Zhongju Wang; Jian Wang; Fei He; Cheng Zhang; Fu Xiong (Molecular Genetics and Genomics, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

The Combined Effects of Increased pCO2 and Warming on a Coastal Phytoplankton Assemblage: From Species Composition to Sinking Rate - Yuanyuan Feng; Fei Chai; Mark L. Wells; Yan Liao; Pengfei Li; Ting Cai; Ting Zhao; Feixue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
In addition to ocean acidification, a significant recent warming trend in Chinese coastal waters has received much attention. However, studies of the combined effects of warming and acidification on natural coastal phytoplankton assemblages here are scarce. We conducted a continuous incubation experiment with a natural spring phytoplankton assemblage collected from the Bohai Sea near Tianjin. Experimental treatments used a full factorial combination of temperature (7 and 11°C) and pCO 2 (400 and 800 ppm) treatments. Results suggest that changes in pCO 2 and temperature had both individual and interactive effects on phytoplankton species composition and elemental stoichiometry. Warming mainly favored the accumulation of picoplankton and dinoflagellate biomass. Increased pCO 2 significantly increased particulate organic carbon to particulate organic phosphorus (C:P) and particulate organic carbon to biogenic silica (C:BSi) ratios, and decreased total diatom abundance; in the meanwhile, higher pCO 2 significantly increased the ratio of centric to pennate diatom abundance. Warming and increased pCO 2 both greatly decreased the proportion of diatoms to dinoflagellates. The highest chlorophyll a biomass was observed in the high pCO 2 , high temperature phytoplankton assemblage, which also had the slowest sinking rate of all treatments. Overall, there were significant interactive effects of increased pCO 2 and warming on dinoflagellate abundance, pennate diatom abundance, diatom vs. dinoflagellates ratio and the centric vs. pennate ratio. These findings suggest that future ocean acidification and warming trends may individually and cumulatively affect coastal biogeochemistry and carbon fluxes through shifts in phytoplankton species composition and sinking rates.

Estimation of the equivalent Mohr–Coulomb parameters using the Hoek–Brown criterion and its application in slope analysis - Yufeng Wei; Wenxi Fu; Fei Ye (European Journal of Environmental and Civil Engineering, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

Paraphyly of the genus Boehmeria (Urticaceae): a response to Liang et al. ‘Relationships among Chinese Boehmeria species and the evolution of various clade’ - Alexandre K. Monro; Steven Dodsworth; Long-Fei Fu; Ib Friis; Christine M. Wilmot-Dear; Olivier Maurin (Plant Systematics and Evolution, 2021)
Boehmeria , as currently circumscribed, comprises 52 species and has a pantropical distribution. Liang et al. propose a sectional classification of Boehmeria based on the phylogenetic analysis of SNP data for 20 species and an additional 10 subspecific taxa of these at the rank of variety or form. They restrict their sampling to species documented in China. We found many shortcomings in the sampling and analyses which we feel have resulted in a misleading phylogeny for the genus and the economically important fibre-plant, Boehmeria nivea . By sampling only Chinese species of this genus for their in-group and using a single distantly related outgroup, Liang et al. have failed to capture the diversity of the genus and so erroneously concluded that it forms a monophyletic group. Previous published research clearly demonstrates that Boehmeria is paraphyletic and polyphyletic, comprising at least four monophyletic groupings most closely related to several genera within the Boehmerieae. For these reasons, the sections that Liang et al. (Ind Crops Prod 148:112092, 2020. https://doi.org/10.1016/j.indcrop.2020.112092) propose for Boehmeria are not effective tools for its classification. The important fibre-plant, Boehmeria nivea , should therefore not be considered as part of the genus Boehmeria for the purposes of crop breeding, but as sister to Archiboehmeria . Breeding programmes for ramie should therefore focus on populations and germplasm of Archiboehmeria atrata . We conclude that poor taxon sampling, overlooking relevant molecular and taxonomic literature, internal conflict within their SNP data and the overinterpretation of low support values has resulted in the erroneous conclusion that Boehmeria represents a monophyletic or ‘natural’ genus.

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Diversity and abundance of resistome in rhizosphere soil - Jian Cao; Fei Liu; Baoli Zhu; Yi Shi; George Fu Gao (Science China Life Sciences, 2020)

Mesoscopic Damage and Fracturing of Heterogeneous Brittle Rocks Based on Three-dimensional Polycrystalline Discrete Element Method - Tao Xu; Teng-Fei Fu; Michael J. Heap; Philip G. Meredith; Thomas M. Mitchell; Patrick Baud (Rock Mechanics and Rock Engineering, 2020)

Patients with radiation enteritis present regulatory T cell impairment associated with CTLA-4 - Xufeng Gong; Genhua Yu; Zongchang Song; Shuqi Huang; Yan Hou; Ning Wang; Wei Zhao; Jingjing Ouyang; Zhengzhou Gu; Haili Hu; Lei Fei; Aixia Fu; et al. (Immunologic Research, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Fishmeal level affects growth performance of Macrobrachium nipponense via regulating protein and lipid metabolism - Qun-Lan Zhou; Su-Fei Jiang; Yi-Wei Xiong; Bo Liu; Cunxin Sun; Zhenting Jiang; Hongtuo Fu (Aquaculture International, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Transcriptional profiling of underground interaction of two contrasting sunflower cultivars with the root parasitic weed Orobanche cumana - Chong Yang; Fei Fu; Na Zhang; Jiansu Wang; Luyang Hu; Faisal Islam; Quanjiang Bai; Xiaopeng Yun; Weijun Zhou (Plant and Soil, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

The influence of DEM spatial resolution on landslide susceptibility mapping in the Baxie River basin, NW China - Zhuo Chen; Fei Ye; Wenxi Fu; Yutian Ke; Haoyuan Hong (Natural Hazards, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

The synergetic effect of pelvic rotation and X-ray offset on radiographic angles of the acetabular cup - Jing-Xin Zhao; Xiu-Yun Su; Zhe Zhao; Ruo-Xiu Xiao; Guo-Fei Sun; Li-Cheng Zhang; Pei-Fu Tang (Medical & Biological Engineering & Computing, 2019)

The anther-specific CYP704B is potentially responsible for MSG26 male sterility in barley - Juan Qi; Fei Ni; Xiao Wang; Meng Sun; Yu Cui; Jiajie Wu; Allan Caplan; Daolin Fu (Theoretical and Applied Genetics, 2019)

Correction to: Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Chronic phencyclidine treatment impairs spatial working memory in rhesus monkeys - Bo Zhang; Fei Xiong; Yuanye Ma; Bing Li; Yu Mao; Zhu Zhou; Hualin Yu; JingHui Li; Chuanyu Li; Juan Fu; Jianhong Wang; Xudong Zhao (Psychopharmacology, 2019)

Long non-coding RNA RP11-6O2.4 indicates poor prognosis and suppresses cell cycle progression through the p38-MAPK signaling pathway in gastric cancer - Yang Feng; Zhiming Fu; Yajun Luo; Wang Tan; Zilin Liu; Pengcheng Ye; Fei Lu; Wanping Xiang; Linghan Tang; Lin Yao; Mengyun Song; Qingmei Huang; et al. (Molecular & Cellular Toxicology, 2019)

Evaluation of the association between urinary cadmium levels below threshold limits and the risk of diabetes mellitus: a dose-response meta-analysis - Fei-Fei Guo; Zhi-Yong Hu; Bing-Yan Li; Li-Qiang Qin; Chunling Fu; Huifang Yu; Zeng-Li Zhang (Environmental Science and Pollution Research, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Evolution Characteristics of Government-Industry-University Cooperative Innovation Network of Electronic Information Industry in Liaoning Province, China - Fei Peng; Qiqi Zhang; Zenglin Han; Yan Ding; Ningning Fu (Chinese Geographical Science, 2019)

Performance Simulation of the Transportation Process Risk of Bauxite Carriers Based on the Markov Chain and Cloud Model - Jianjun Wu; Shenping Hu; Yongxing Jin; Jiangang Fei; Shanshan Fu (Journal of Marine Science and Engineering, 2019)
China imports a large quantity of bauxite each year. Bauxite in fine particles with high moisture has a high risk of liquefaction during the maritime transportation process, which is harmful to the stability and safety of the carrier. To ensure safe shipping, it is necessary to pay attention to the effects of the operation of cargo, the ship’s maneuvering and the ocean environment during the whole transportation process. The simulation of the process risk helps to develop measures to intervene with the cargo behavior to keep the risk to an acceptable level. This study examined the transportation process of a bauxite carrier using the Markov Chain method at different stages of loading, unberthing, departure and sea navigation. Based on the risk transfer matrix of the operational status at different stages of transportation, a cloud simulation model was developed to analyze the transportation process risk of a ship carrying bulk bauxite. Results: the research revealed that the risk evolution rule of the solid bulk cargoes with potential liquefaction during the transportation process, especially bauxite. The risk alteration during the prophase of the transportation process conforms to the rule of the “spoon curve”. Conclusions: a simulation model of the process risk based on the Markov Chain Cloud is suitable for the simulation analysis of the transportation risk of the bulk bauxite carrier. The outcomes of this study may contribute to better safety management to prevent the occurrence of ship capsizing.

Genomic and biological characterization of the Vibrio alginolyticus-infecting “Podoviridae” bacteriophage, vB_ValP_IME271 - Fei Li; Shaozhen Xing; Kaifei Fu; Shuping Zhao; Jianfei Liu; Yigang Tong; Lijun Zhou (Virus Genes, 2019)

Genome-wide identification and functional analysis of the splicing component SYF2/NTC31/p29 across different plant species - Yuan Tian; Mo-Xian Chen; Jing-Fang Yang; H. H. K. Achala; Bei Gao; Ge-Fei Hao; Guang-Fu Yang; Zhi-Yong Dian; Qi-Juan Hu; Di Zhang; Jianhua Zhang; Ying-Gao Liu (Planta, 2019)

Mild Hypothermia Prevents NO-Induced Cytotoxicity in Human Neuroblastoma Cells Via Induction of COX-2 - Bing-Bing Lei; Fei Ju; Qi-Ran Fu; Xin Yuan; Wen-Xin Song; Guo-Qin Ji; Kai-Yu Lei; Lei Wang; Bin-Feng Cheng; Mian Wang; Hai-Jie Yang (Journal of Molecular Neuroscience, 2019)

Optimizing nitrogen management to balance rice yield and environmental risk in the Yangtze River’s middle reaches - Jing Wang; Penghao Fu; Fei Wang; Shah Fahad; Pravat K. Mohapatra; Yutiao Chen; Congde Zhang; Shaobing Peng; Kehui Cui; Lixiao Nie; Jianliang Huang (Environmental Science and Pollution Research, 2019)

The effects of simulated acid rain on internal nutrient cycling and the ratios of Mg, Al, Ca, N, and P in tea plants of a subtropical plantation - Xiao-Fei Hu; An-Qi Wu; Fang-Chao Wang; Fu-Sheng Chen (Environmental Monitoring and Assessment, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Surface mulching and a sandy soil interlayer suppress upward enrichment of salt ions in salt-contaminated field - Jianyong Wang; Huiming Liu; Shaoming Wang; Yingxia Liu; Zhengguo Cheng; Guangqiang Fu; Fei Mo; Youcai Xiong (Journal of Soils and Sediments, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Down-regulation of microRNA-216a confers protection against yttrium aluminium garnet laser-induced retinal injury via the GDNF-mediated GDNF/GFRα1/RET signalling pathway - Xi-Bin Hu; Shu-Hua Fu; Qi Luo; Jian-Zhong He; Yan-Fei Qiu; Wei Lai; Min Zhong (Journal of Biosciences, 2018)

Artificial intelligence in drug design - Feisheng Zhong; Jing Xing; Xutong Li; Xiaohong Liu; Zunyun Fu; Zhaoping Xiong; Dong Lu; Xiaolong Wu; Jihui Zhao; Xiaoqin Tan; Fei Li; Xiaomin Luo; et al. (Science China Life Sciences, 2018)

Poststack internal multiples attenuation based on virtual events - Meng Chen; Jia-Hui Liu; Yong-Fu Cui; Tian-Yue Hu; Fei-Xu Chen; Wei-Kang Kuang; Zhen Zhang (Applied Geophysics, 2018)

Remapping of the stripe rust resistance gene Yr10 in common wheat - Cuiling Yuan; Jingzheng Wu; Baiqiang Yan; Qunqun Hao; Chaozhong Zhang; Bo Lyu; Fei Ni; Allan Caplan; Jiajie Wu; Daolin Fu (Theoretical and Applied Genetics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Detoxification of aflatoxins on prospective approach: effect on structural, mechanical, and optical properties under pressures - Yong-Kai Wei; Xiao-Miao Zhao; Meng-Meng Li; Jing-Xin Yu; Selvaraj Gurudeeban; Yan-Fei Hu; Guang-Fu Ji; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Molecular characterization of a stress-induced NAC gene, GhSNAC3, from Gossypium hirsutum - Zhan-Ji Liu; Fei Li; Li-Guo Wang; Ren-Zhong Liu; Jun-Jun Ma; Ming-Chuan Fu (Journal of Genetics, 2018)

Seismic responses of the steel-strip reinforced soil retaining wall with full-height rigid facing from shaking table test - Li-cong Cao; Xiao Fu; Zhi-jia Wang; Yong-yi Zhou; Fei-cheng Liu; Jian-jing Zhang (Journal of Mountain Science, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

The role of shallow convection in promoting the northward propagation of boreal summer intraseasonal oscillation - Fei Liu; Jiuwei Zhao; Xiouhua Fu; Gang Huang (Theoretical and Applied Climatology, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Genetic variation and association mapping of aphid (Macrosiphoniella sanbourni) resistance in chrysanthemum (Chrysanthemum morifolium Ramat.) - Xiao Fu; Jiangshuo Su; Kaili Yu; Yifan Cai; Fei Zhang; Sumei Chen; Weimin Fang; Chen Fadi; Zhiyong Guan (Euphytica, 2018)

Morphological and genetic characterization of a new cytoplasmic male sterility system (oxa CMS) in stem mustard (Brassica juncea) - Shuangping Heng; Sansan Liu; Chunxiu Xia; HongYu Tang; Fei Xie; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2018)

Melt Extrusion for a High Melting Point Compound with Improved Solubility and Sustained Release - Jiannan Lu; Sakae Obara; Fei Liu; Wanyi Fu; Wen Zhang; Shingo Kikuchi (AAPS PharmSciTech, 2018)

New progress in understanding the origins of modern humans in China - Xing Gao; Fei Peng; QiaoMei Fu; Feng Li (Science China Earth Sciences, 2017)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Increasing acidity of rain in subtropical tea plantation alters aluminum and nutrient distributions at the root-soil interface and in plant tissues - Xiao-Fei Hu; Fu-Sheng Chen; Michael L. Wine; Xiang-Min Fang (Plant and Soil, 2017)

Preparation and Evaluation of Diosgenin Nanocrystals to Improve Oral Bioavailability - Cui-zhe Liu; Jin-hua Chang; Lin Zhang; He-fei Xue; Xi-gang Liu; Pei Liu; Qiang Fu (AAPS PharmSciTech, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

An overview of nanomaterials applied for removing dyes from wastewater - Zhengqing Cai; Youmin Sun; Wen Liu; Fei Pan; Peizhe Sun; Jie Fu (Environmental Science and Pollution Research, 2017)

Effects of water-saving irrigation on weed infestation and diversity in paddy fields in East China - Yufeng Luo; Haolong Fu; Yujiang Xiong; Zhao Xiang; Fei Wang; Yves Christian Bugingo; Shahbaz Khan; Yuanlai Cui (Paddy and Water Environment, 2017)

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Two new ent -atisane diterpenoids from the whole plants of Euphorbia wallichii - Yi Kuang; Shen-Yuan Fu; Fei Wang; Fu-Cai Ren; Dong-Feng Yang; Sheng-Xiang Yang; Yuan Gao (Natural Product Research, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Shape-based object extraction in high-resolution remote-sensing images using deep Boltzmann machine - Qichang Wu; Wenhui Diao; Fangzheng Dou; Xian Sun; Xinwei Zheng; Kun Fu; Fei Zhao (International Journal of Remote Sensing, 2016)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Papaya CpERF9 acts as a transcriptional repressor of cell-wall-modifying genes CpPME1/2 and CpPG5 involved in fruit ripening - Chang-Chun Fu; Yan-Chao Han; Xiu-Ye Qi; Wei Shan; Jian-Ye Chen; Wang-Jin Lu; Jian-Fei Kuang (Plant Cell Reports, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Shear strength features of soils developed from purple clay rock and containing less than two-millimeter rock fragments - Shou-qin Zhong; Mang Zhong; Chao-fu Wei; Wei-hua Zhang; Fei-nan Hu (Journal of Mountain Science, 2016)

Two new compounds, deacetylisowortmins A and B, isolated from an endophytic Fungus, Talaromyces wortmannii LGT-4 - Guang-Chao Fu; Zhong-Duo Yang; Shuang-Yan Zhou; Hai-Tao Yu; Fei Zhang; Xiao-Jun Yao (Natural Product Research, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

A new plant assemblage from the Middle Triassic volcanic tuffs of Pingchuan, Gansu, northwestern China and its paleoenvironmental significance - Fu-Jun Ma; Qiu-Jun Wang; Jun-Ling Dong; Hao-Fei Wang; Zi-Xi Wang; Feng-Tai Zhang; Bai-Nian Sun (PalZ, 2016)

Relationship between SST anomalies and the intensity of intraseasonal variability - Fei Liu; Lei Zhou; Jian Ling; Xiouhua Fu; Gang Huang (Theoretical and Applied Climatology, 2016)

Earthworms facilitate the stabilization of pelletized dewatered sludge through shaping microbial biomass and activity and community - Xiaoyong Fu; Guangyu Cui; Kui Huang; Xuemin Chen; Fusheng Li; Xiaoyu Zhang; Fei Li (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Spatial analysis of meteorological drought return periods in China using Copulas - Xiong-Fei Liu; Shi-Xin Wang; Yi Zhou; Fu-Tao Wang; Guang Yang; Wen-Liang Liu (Natural Hazards, 2016)

Elemental sulfur in northern South China Sea sediments and its significance - Qi Lin; JiaSheng Wang; ShaoYing Fu; HongFeng Lu; QingTao Bu; RongXiao Lin; Fei Sun (Science China Earth Sciences, 2015)

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study - Wenjia Zhu; Xiaoling Fu; Fang Cui; Fei Yang; Yuting Ren; Xiaoyun Zhang; Xiaolan Zhang; Zhaohui Chen; Li Ling; Xusheng Huang (Journal of Molecular Neuroscience, 2015)

Lipophilic constituents from two processed products and three different parts of Changium smyrnioides Wolff. - Gang-Gang Bai; Fei Yuan; Fu-Qiang Li; Kun-Jun Mao; Ping Zhou; Jian-Wei Chen; Xiang Li (Natural Product Research, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Spectral Characteristics of Tropical Anvils Obtained by Combining TRMM Precipitation Radar with Visible and Infrared Scanner Data - Yuan-Jian Yang; Da-Ren Lu; Yun-Fei Fu; Feng-Jiao Chen; Yu Wang (Pure and Applied Geophysics, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Comparative responses of two dominant Antarctic phytoplankton taxa to interactions between ocean acidification, warming, irradiance, and iron availability - Kai Xu; Fei‐Xue Fu; David A. Hutchins (Limnology and Oceanography, 2014)
We investigated the responses of the ecologically dominant Antarctic phytoplankton species Phaeocystis antarctica (a prymnesiophyte) and Fragilariopsis cylindrus (a diatom) to a clustered matrix of three global change variables (CO 2 , mixed‐layer depth, and temperature) under both iron (Fe)‐replete and Fe‐limited conditions based roughly on the Intergovernmental Panel on Climate Change (IPCC) A2 scenario: (1) Current conditions, 39 Pa (380 ppmv) CO 2 , 50 µmol photons m −2 s −1 light, and 2°C; (2) Year 2060, 61 Pa (600 ppmv) CO 2 , 100 µmol photons m −2 s −1 light, and 4°C; (3) Year 2100, 81 Pa (800 ppmv) CO 2 , 150 µmol photons m −2 s −1 light, and 6°C. The combined interactive effects of these global change variables and changing Fe availability on growth, primary production, and cell morphology are species specific. A competition experiment suggested that future conditions could lead to a shift away from P. antarctica and toward diatoms such as F. cylindrus. Along with decreases in diatom cell size and shifts from prymnesiophyte colonies to single cells under the future scenario, this could potentially lead to decreased carbon export to the deep ocean. Fe : C uptake ratios of both species increased under future conditions, suggesting phytoplankton of the Southern Ocean will increase their Fe requirements relative to carbon fixation. The interactive effects of Fe, light, CO 2 , and temperature on Antarctic phytoplankton need to be considered when predicting the future responses of biology and biogeochemistry in this region.

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Effects of grazing exclusion on soil carbon and nitrogen storage in semi-arid grassland in Inner Mongolia, China - Xing Wu; Zongshan Li; Bojie Fu; Fei Lu; Dongbo Wang; Huifeng Liu; Guohua Liu (Chinese Geographical Science, 2014)

Quantitative dietary isoleucine requirement of juvenile Pacific white shrimp, Litopenaeus vannamei (Boone) reared in low-salinity water - Fu-Jia Liu; Yong-Jian Liu; Li-Xia Tian; Xue-Fei Li; Zhi-Hao Zhang; Hui-Jun Yang; Zhen-Yu Du (Aquaculture International, 2014)

The genome sequence of a novel simian adenovirus in a chimpanzee reveals a close relationship to human adenoviruses - Chenglin Zhou; Hua Tian; Xiaochun Wang; Wei Liu; Shixing Yang; Quan Shen; Yan Wang; Bin Ni; Shengxia Chen; Xingli Fu; Rongmei Fei; Wen Zhang (Archives of Virology, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

Distribution of Polychlorinated Biphenyls in Soil Around Three Typical Industrial Sites in Beijing, China - Yong-Fei Zhang; Shan Fu; Yuan Dong; Hai-Feng Nie; Zheng Li; Xin-Chun Liu (Bulletin of Environmental Contamination and Toxicology, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Acceleration effect of amino acid supplementation on glycerol assimilation by Escherichia coli in minimal medium - Gang Xiang; Jiang Li; JiFu Duan; Fei Shao; Jiajie Xu; Shuilin Fu; Heng Gong (Biotechnology Letters, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Colimitation of the unicellular photosynthetic diazotroph Crocosphaera watsonii by phosphorus, light, and carbon dioxide - Nathan S. Garcia; Fei-Xue Fu; David A. Hutchins (Limnology and Oceanography, 2013)
We describe interactive effects of total phosphorus (total P = 0.1–4.0 µmol L −1 ; added as H 2 NaPO 4 ), irradiance (40 and 150 µmol quanta m −2 s −1 ), and the partial pressure of carbon dioxide (; 19 and 81 Pa, i.e., 190 and 800 ppm) on growth and CO 2 ‐ and dinitrogen (N 2 )‐fixation rates of the unicellular N 2 ‐fixing cyanobacterium Crocosphaera watsonii (WH0003) isolated from the Pacific Ocean near Hawaii. In semicontinuous cultures of C. watsonii , elevated positively affected growth and CO 2 ‐ and N 2 ‐fixation rates under high light. Under low light, elevated positively affected growth rates at all concentrations of P, but CO 2 ‐ and N 2 ‐fixation rates were affected by elevated only when P was low. In both high‐light and low‐light cultures, the total P requirements for growth and CO 2 ‐ and N 2 ‐fixation declined as increased. The minimum concentration (C min ) of total P and half‐saturation constant (K ʽ ) for growth and CO 2 ‐ and N 2 ‐fixation rates with respect to total P were reduced by 0.05 µmol L −1 as a function of elevated . We speculate that low P requirements under high resulted from a lower energy demand associated with carbon‐concentrating mechanisms in comparison with low‐ cultures. There was also a 0.10 µmol L −1 increase in C min and K ʽ for growth and N 2 fixation with respect to total P as a function of increasing light regardless of concentration. We speculate that cellular P concentrations are responsible for this shift through biodilution of cellular P and possibly cellular P uptake systems as a function of increasing light. Changing concentrations of P, CO 2 , and light have both positive and negative interactive effects on growth and CO 2 ‐, and N 2 ‐fixation rates of unicellular oxygenic diazotrophs like C. watsonii .

SCY1-like 1 binding protein 1 (SCYL1-bp1) interacts with p53-induced RING H2 protein (Pirh2) after traumatic brain injury in rats - Jian Chen; Feihui Zou; Hongran Fu; Hui Mao; Mingjie Gong; Lanchun Ni; Xide Xu; Jinlong Shi; Kaifu Ke; Maohong Cao; Fei Zhou; Wei Shi (Journal of Molecular Histology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

A comparison of two kinds of eastward-moving mesoscale vortices during the mei-yu period of 2010 - ShenMing Fu; Fei Yu; DongHai Wang; RuDi Xia (Science China Earth Sciences, 2013)

Monsoon and eddy forcing of chlorophyll- a variation in the northeast South China Sea - Tao Xian; Liang Sun; Yuan-Jian Yang; Yun-Fei Fu (International Journal of Remote Sensing, 2012)

RETRACTED ARTICLE: A 2-D DIGE analysis of simulated acid rain-responsive proteins in Pinus massoniana needles - Ting-Wu Liu; Wen-Jun Hu; Xiao-Qin Wang; Li Niu; Bin Fu; Fei-Hua Wu; Zhen-Ming Pei; Hai-Lei Zheng (Trees, 2012)

Review of melting experiments on carbonated eclogite and peridotite: insights into mantle metasomatism - Peng-Fei Zhang; Yan-Jie Tang; Yan Hu; Hong-Fu Zhang; Ben-Xun Su; Yan Xiao; M. Santosh (International Geology Review, 2012)

Reduction of the thermocline feedback associated with mean SST bias in ENSO simulation - Baoqiang Xiang; Bin Wang; Qinghua Ding; Fei–Fei Jin; Xiouhua Fu; Hyung-Jin Kim (Climate Dynamics, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Protective effects of 7-difluoromethyl-5,4′-dimethoxygenistein against human aorta endothelial injury caused by lysophosphatidyl choline - Fei Liu; Jian-Guo Cao; Cheng Li; Jin-Seng Tan; Xiao-Hua Fu (Molecular and Cellular Biochemistry, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Soil phosphorus fractions and tree phosphorus resorption in pine forests along an urban-to-rural gradient in Nanchang, China - Xiao-Fei Hu; Fu-Sheng Chen; Gregory Nagle; Yun-Ting Fang; Ming-Quan Yu (Plant and Soil, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Identification of annexin A1 as a proinvasive and prognostic factor for lung adenocarcinoma - Ying-Fu Liu; Peng-Fei Zhang; Mao-Yu Li; Quo-Qing Li; Zhu-Chu Chen (Clinical & Experimental Metastasis, 2011)

Cloud variations under subtropical high conditions - Sha Feng; Qi Liu; Yun-Fei Fu (Advances in Atmospheric Sciences, 2011)

Effects of changing p CO 2 and phosphate availability on domoic acid production and physiology of the marine harmful bloom diatom Pseudo‐nitzschia multiseries - Jun Sun; David A. Hutchins; Yuanyuan Feng; Erica L. Seubert; David A. Caron; Fei-Xue Fu (Limnology and Oceanography, 2011)
Some members of the diatom genus Pseudo‐nitzschia produce the toxin domoic acid (DA), which through trophic transfer causes mass mortalities of wildlife, shellfish harvesting closures, and risks to human health. Nutrient and micronutrient limitation have been shown to regulate DA production. This study tested the hypothesis that changing partial pressure of CO 2 ( p CO 2 ) can interact with nutrient limitation to help determine cellular DA levels, an environmentally relevant issue in light of current increases in atmospheric p CO 2 . Cultures of the toxic species Pseudo‐nitzschia multiseries were incubated using semicontinuous methods under a matrix of three p CO 2 conditions: ∼ 22 Pa (220 ppm), ∼ 41 Pa (400 ppm), and ~ 74 Pa (730 ppm), and two phosphate concentrations: 20 μmol L −1 , P‐replete; and 0.5 μmol L −1 , P‐limited. DA production was regulated by both p CO 2 and phosphate availability. DA concentrations were 30–50 times higher in P‐limited cultures compared to P‐replete ones, at the same p CO 2 levels. Increasing CO 2 levels stimulated DA production under both nutrient conditions, but especially in P‐limited cultures, where DA levels increased approximately four times over the p CO 2 range examined. Growth rates, primary productivity, photosynthesis vs. irradiance parameters, and cellular elemental ratios also responded interactively to the availability of both CO 2 and phosphate. Our results raise the possibility that growth rates and toxicity of the diatom Pseudo‐nitzschia multiseries could increase substantially in the future high‐CO 2 ocean, suggesting a potentially escalating negative effect of this harmful algal bloom species on the future marine environment.

Quantitative trait loci analysis for rice seed vigor during the germination stage - Zhou-fei Wang; Jian-fei Wang; Yong-mei Bao; Fu-hua Wang; Hong-sheng Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Targeted antitumor effect induced by hTERT promoter mediated ODC antisense adenovirus - Wei Wang; Bin Jin; Wei Li; Chun-Xiao Xu; Fu-Ai Cui; Bin Liu; Yun-Fei Yan; Xian-Xi Liu; Xiu-Li Wang (Molecular Biology Reports, 2010)

The biophysical responses of the upper ocean to the typhoons Namtheun and Malou in 2004 - Yuan-Jian Yang; Liang Sun; Qi Liu; Tao Xian; Yun-Fei Fu (International Journal of Remote Sensing, 2010)

Sleeping Sites of Rhinopithecus brelichi at Yangaoping, Guizhou - Zuo-Fu Xiang; Shuai-Guo Nie; Zong-Fei Chang; Fu-Wen Wei; Ming Li (International Journal of Primatology, 2010)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

One-step preparation of antibody and oligonucleotide dual-labeled gold nanoparticle bio-probes and their properties - Xiao-li Kong; Fei-yan Qiao; Hui Qi; Fu-rong Li (Biotechnology Letters, 2008)

Extensive population expansion of Pedicularis longiflora (Orobanchaceae) on the Qinghai‐Tibetan Plateau and its correlation with the Quaternary climate change - FU‐SHENG YANG; YU‐FEI LI; XIN DING; XIAO‐QUAN WANG (Molecular Ecology, 2008)
The Qinghai‐Tibetan Plateau (QTP) is thought to be more strongly affected by the Quaternary glaciations than most other regions of the same latitude. It would be of great interest to investigate the population genetic structure of organisms distributed on the platform and its correlation with the Quaternary climatic oscillations. Here we used the chloroplast (cp)DNA trn T‐ trn F sequence to study genetic variation and phylogeography of Pedicularis longiflora , an alpine herb with extensive distribution on the QTP. Based on a range‐wide sampling comprising 41 populations and 910 individuals, we detected 30 cpDNA haplotypes that were divided into five clades by phylogenetic and network analyses and a strong phylogeographical structure. All haplotypes but one in the three basal clades occur exclusively in the southeast QTP, whereas haplotypes in the young clade V occupy almost the whole species range. In particular, the young haplotype H18 occurs in 420 individuals, even at a frequency of 100% in some QTP platform populations and the Altai population. The haplotype distribution pattern, together with molecular clock estimation and mismatch distribution analysis, suggests that the southeast QTP was either a refuge for P . longiflora during the Quaternary climatic change or is the place of origin of the species. The present wide distribution of the species on the QTP platform has resulted from recent population expansions which could be dated back to 120 000–17 000 years ago, a period mostly before the last glacial maximum. The possible relationships among geographic genetic structure, climatic change and species diversification in Pedicularis are also discussed.

Interactions between changing pCO2, N2 fixation, and Fe limitation in the marine unicellular cyanobacterium Crocosphaera - Fei-Xue Fu; Margaret R. Mulholland; Nathan S. Garcia; Aaron Beck; Peter W. Bernhardt; Mark E. Warner; Sergio A. Sañudo-Wilhelmy; David A. Hutchins (Limnology and Oceanography, 2008)
We examined the physiological responses of steady‐state iron (Fe)‐replete and Fe‐limited cultures of the biogeochemically critical marine unicellular diazotrophic cyanobacterium Crocosphaera at glacial (19 Pa; 190 ppm), current (39 Pa; 380 ppm), and projected year 2100 (76 Pa; 750 ppm) CO 2 levels. Rates of N 2 and CO 2 fixation and growth increased in step with increasing partial pressure of CO 2 (pCO 2 ), but only under Fe‐replete conditions. N 2 and carbon fixation rates at 75 Pa CO 2 were 1.4‐1.8‐fold and 1.2‐2.0‐fold higher, respectively, relative to those at present day and glacial pCO 2 levels. In Fe‐replete cultures, cellular Fe and molybdenum quotas varied threefold and were linearly related to N 2 fixation rates and to external pCO 2 . However, N 2 fixation and trace metal quotas were decoupled from pCO 2 in Fe‐limited Crocosphaera . Higher CO 2 and Fe concentrations both resulted in increased cellular pigment contents and affected photosynthesis vs. irradiance parameters. If these results also apply to natural Crocosphaera populations, anthropogenic CO 2 enrichment could substantially increase global oceanic N 2 and CO 2 fixation, but this effect may be tempered by Fe availability. Possible biogeochemical consequences may include elevated inputs of new nitrogen to the ocean and increased potential for Fe and/or phosphorus limitation in the future high‐CO 2 ocean, and feedbacks to atmospheric pCO 2 in both the near future and over glacial to interglacial timescales.

Ischemic preconditioning induces chaperone hsp70 expression and inhibits protein aggregation in the CA1 neurons of rats - Peng-Fei Ge; Tian-Fei Luo; Ji-Zhou Zhang; Da-Wei Chen; Yong-Xin Luan; Shuang-Lin Fu (Neuroscience Bulletin, 2008)

Deep lingual arterial chemoembolization of tongue carcinoma with microcapsuled anticancer drug - Hong He; Jian-qi Huang; Fei-yun Ping; Guan-fu Chen; Su-zhan Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Isolation of a strain of Acidithiobacillus caldus and its role in bioleaching of chalcopyrite - Qiu Guan Zhou; Fu Bo; Zhou Hong Bo; Liu Xi; Gao Jian; Liu Fei Fei; Chen Xin Hua (World Journal of Microbiology and Biotechnology, 2007)

Effects of nitrogen fertilizer application rates on nitrate nitrogen distribution in saline soil in the Hai River Basin, China - Fei Yin; Bojie Fu; Renzhao Mao (Journal of Soils and Sediments, 2007)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

Effect of light on growth, pigmentation and N2 fixation of cultured Trichodesmium sp. from the Great Barrier Reef lagoon - Peter R. F. Bell; Fei-Xue Fu (Hydrobiologia, 2005)

Laboratory culture studies of Trichodesmium isolated from the Great Barrier Reef Lagoon, Australia - Peter R. F. Bell; Philippa J. R. Uwins; Ibrahim Elmetri; Julie A. Phillips; Fei-Xue Fu; Anya J.E. Yago (Hydrobiologia, 2005)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

The receptor tyrosine kinase inhibitor SU11248 impedes endothelial cell migration, tubule formation, and blood vessel formation in vivo, but has little effect on existing tumor vessels - Katherine L. Osusky; Dennis E. Hallahan; Allie Fu; Fei Ye; Yu Shyr; Ling Geng (Angiogenesis, 2004)

Rapid clonal propagation of Dioscorea zingiberensis - Yongqin Chen; Jinyu Fan; Fei Yi; Zhongxun Luo; Yunsheng Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Growth, N2 fixation and photosynthesis in a cyanobacterium, Trichodesmium sp., under Fe stress - Fei-xue Fu; P.R.F. Bell (Biotechnology Letters, 2003)

Scale-dependent spatial heterogeneity of vegetation in Mu Us sandy land, a semi-arid area of China - Yu Fu Chen; Fei Hai Yu; Ming Dong (Plant Ecology, 2002)

New Method to Obtain Ultrasonic Angle Independent Doppler Color Images Using a Sector Transducer - Ding-Yu Fei; Cai-Ting Fu (Annals of Biomedical Engineering, 1999)

Oxygen and hydrogen isotope geochemistry of gneisses associated with ultrahigh pressure eclogites at Shuanghe in the Dabie Mountains - Bin Fu; Yong-Fei Zheng; Zhengrong Wang; Yilin Xiao; Bing Gong; Shuguang Li (Contributions to Mineralogy and Petrology, 1999)